Complex evolutionary history of Rosales mediated by extensive incomplete lineage sorting and hybridization - Luxian Liu; Weiwei Lv; Douglas E. Soltis; Hans Peter Comes; Yonghua Zhang; Yu Shi; Shufen Li; Meizhen Wang; Wujun Gao; Pan Li (Molecular Phylogenetics and Evolution, 2026)

Quality formation mechanism of shiitake mushrooms during multiphase microwave drying (MMD) - Zhenbin Liu; Jia Luo; Jiayi Zhang; Rui Weng; Wenchao Liu; Hongbo Li; Huan Cheng; Dong Wang; Hengchao E; Lu Tian; Haizhen Mo; Liangbin Hu (Food Control, 2026)

AIE-active dual-pore covalent organic framework for colorimetric/fluorescence detection and degradation of perfluorooctanoic acid - Tianyuan Yu; Shuai Liu; Shaoxi He; Guoyi Pu; Xi Zhang; Yanxiong Liu; Wenyu He; Ziyu Bao; Zezhou Zhao; Jiahui Liu; Fei Li; Rong Sheng Li; et al. (Chemical Engineering Journal, 2026)

Microplastic sedimentary records in a shallow lake of North China: Identifiable responses to hydrological and socio-economic drivers - Yutao Zuo; Yawen Ge; Xin Mao; Yuhang Xia; Xinjie Li; Changhong Liu; Huiyuan Jia; Yuecong Li; Ke Zhang; Michael E. Meadows (Water Research, 2026)

Embedding bio-Fenton in a hybrid membrane biofilm reactor enhances the treatment of antibiotic-contaminated saline water - Wei Li; Ying-Lian Lan; Xu Zhang; Yi-Hao Luo; Yu-Xiang Zhao; Ju-Ying Lei; Yong-Di Liu; Bruce E. Rittmann (Water Research, 2026)

An integrated multiscale air quality modelling framework for industrial park pollution: Linking local emissions to regional transport - Tao Wang; Jie Li; Joshua S. Fu; Wei Wang; Bing Liu; Bin Zhao; Yibo Zhang; Jinxiu Pan; Feng Sun; Xiu’e Shen; Zhe Wang; Xiao Tang; et al. (Journal of Environmental Sciences, 2026)

Maize attainable yields across China reveal unrealized potential for sustainable food security - Jingjing Wang; Zhijuan Liu; Zhenkang Yang; E Li; Jiangjiang Xia; Jingjin Gong; Huihui Qu; Tao Li; Xiaomao Lin; Xiaoguang Yang (Field Crops Research, 2026)

Residues, drivers, and health implications of herbicides in typical black soil regions of China: Soil-crop system linkage and targeted human risk - Le Jian; Hanqiang Liu; Wenyou Hu; Peter E. Holm; Rui Li; Wenxue Niu; Feng Liu; Yuguo Zhao; Yongcun Zhao; Biao Huang (Environmental Pollution, 2026)

Distinct ages and mantle sources for Southern Ocean oceanic plateaus - Peter C. Davidson; Jörg Geldmacher; Yuji Ichiyama; Jia Liu; Folkmar Hauff; Anthony A.P. Koppers; Daniel E. Heaton; Daniel A. Frick; Kaj Hoernle; Odysseas A. Archontikis; Sietske J. Batenburg; Peter Bijl; et al. (Earth and Planetary Science Letters, 2026)

Cyclodextrin-engineered bioinspired nanozyme microneedle for adaptive theranostic regulation of hyperuricemia and gout - Xu-Wei Qi; Hua-Zhou Niu; Ya-Hui Chen; Ye-Tao Zhang; Jing Li; Zu-E Hu; Jia-Xin Wang; Yi-Qi Liu; Bang-Jing Li; Sheng Zhang (Carbohydrate Polymers, 2026)

Salmonella risk prediction in poultry farms via deep learning image classification Models, Cross-Region Validation, and edge computing - Venkat Umesh Chandra Bodempudi; Guoming Li; Adelumola Oladeinde; Michael J. Rothrock; Samuel E Aggrey; Tongshuai Liu; Sai Akshitha Reddy Kota; Geng Yuan; Sravan Sai Rahul Nalla (Computers and Electronics in Agriculture, 2026)

Unraveling the Co-release Dynamics of Micro/nanoplastics and Toxic Transformation Products from Weathered Single-Use Plastics - Guoxin Li; Ziyi Liu; Yongrong Hu; E Xiang; Shangsi Lv; Shuofei Dong; Dong Yan; Yuxiong Huang (Water Research, 2026)

Zn-La staged modification of reed biochar for adsorption of tetracycline hydrochloride and mechanism study - Zhengqi Liang; Xiongyan Gao; Yushan Li; Xu Liu; Boxing An; Yingying Zuo; Ling Wang; Jiahui Fu; Meili E (Journal of Water Process Engineering, 2026)

Allochthonous particulate organic carbon in blue carbon ecosystems: Implications for accounting, stability, and policy - Anirban Akhand; Inés Mazarrasa; Stacey M. Trevathan-Tackett; K.M.G. Mostofa; Abhra Chanda; Hongbin Liu; Hiroshi Sakugawa; Si-Liang Li; Cong-Qiang Liu; Catherine E. Lovelock; Paul Lavery; Hilary Kennedy; et al. (Journal of Environmental Management, 2026)

Bioaugmentation of Rhodococcus ruber F1 achieved simultaneous removals of benzophenone-3 and ammonium - Fei Liu; Chenyu Li; Yuxuan Zhou; Mo Li; Zhicheng Pan; Fu Chen; Yongming Zhang; Bruce E. Rittmann (International Biodeterioration & Biodegradation, 2026)

Enhancing reproducibility in neuroimaging with containerized archival - Michael E. Kim; Praitayini Kanakaraj; Yihao Liu; Trent Schwartz; Zhiyuan Li; Nancy R. Newlin; Chenyu Gao; Kurt G. Schilling; Shunxing Bao; Baxter P. Rogers; Bennett A. Landman; Karthik Ramadass (Brain Imaging and Behavior, 2026)
Ensuring reproducibility in scientific research is crucial for validating findings, advancing knowledge, and fostering trust within the scientific community. Containerization of code is a widespread practice to help ensure reproducibility in neuroimaging research. However, there exists no universal method of sharing containers, nor is it feasible to broadly enforce rules due to the diversity of research practices. We posit that container sharing should include 1.) public availability, 2.) self-contained documentation, and 3.) procedures to ensure consistency of the container and its expected outputs. We demonstrate an approach for publicly releasing three separate containers using Zenodo. Our proposed method fulfills the design criteria for container sharing while incurring minimal overhead. As there are several tools available to distribute and maintain containers already, we discuss available alternatives.

Cold seep environment shapes the structure and metabolic potential of mesopelagic fish gut microbiota - Xiyue Yang; Chunhou Li; Yong Liu; Zuozhi Chen; Yan′e Jiang; Min Li; Yancong Cai; Jian Zou; Shannan Xu; Yayuan Xiao; Yu Liu; Dajuan Zhang; et al. (Regional Studies in Marine Science, 2026)

Integrative genomic analyses reveal genetic structuring and cyto-nuclear incongruences within the Corbicula species complex in China - Yangxin Tang; Linwei Liu; Jie Pi; Xinhua Liu; Jianguo Xiang; Joong-Ki Park; Neil E. Coughlan; Deliang Li (Molecular Phylogenetics and Evolution, 2026)

Pore structure evolution in organic-rich shale during thermal maturation: Insights from hydrous pyrolysis of two lacustrine kerogens - Fengtian Bai; Lee A. Stevens; Clement N. Uguna; Wei Li; Will Meredith; Colin E. Snape; Christopher H. Vane; Yumin Liu; Chenggong Sun (Fuel, 2026)

MgI2 immobilized nitrogen and phosphorus co-doped hollow carbon cubes as a multifunctional host for high-performance lithium‑sulfur batteries - Sheng Liang; Cong Li; Zi-Hao Chen; Lei Hu; Xin Liang; Ling-Li Liu; Li-Li Wang; Ning-Ning Zhou; Bin Chen; Wen-Yu Gu; San-E Zhu (Chemical Engineering Journal, 2026)

Metallogenic Mechanism for the Deep Part of the Jiaojia Gold Zone in the Eastern North China Craton (Jiaodong): Constrains from Pyrite Re-Os Geochronology, in-situ Trace Elements and Sulfur Isotope Compositions - Naijie Chi; Zuozhen Han; Xuefeng Yu; Wei Shan; Chuan’e Liu; Xiufeng Wang; Zengsheng Li; Shenghu Li; Chenxi Zhang; Xiangxian Ma (Journal of Earth Science, 2026)

Discovery of novel cinnamic acid derivatives with anti-Helicobacter pylori mechanism - Yonglian Li; Xiuya Ye; Yuan’e Yang; Wenfeng Liu; Suqing Zhao (Molecular Diversity, 2026)

The role of ecosystem conservation and restoration in achieving the SDGs - Yizhong Huan; Guangjin Zhou; Alice C. Hughes; Xiaoyun Li; Peng Hou; Marco Lambertini; Tao Liang; Wenwu Zhao; Binoy Sarkar; Alexandre Betinardi Strapasson; Yiming Su; Xiaoman Liu; et al. (Science Bulletin, 2026)

A field-scale model using an integrated framework for evaluating food and water dynamics in agrivoltaics in three-dimensional space - Anh H. Nguyen; Yaoze Liu; Siyu Li; Zhuohang Wu; Majdi R. Abou Najm; Liming Zhou; Xiaobo Xue Romeiko; Richard R. Perez; Mark E. Uchanski; Jennifer M. Bousselot; Hu Liu; Chuandong Wu (Journal of Cleaner Production, 2026)

Triplex-helix molecular beacon-enabled CRISPR/Cas12a biosensor for sensitive detection of SARS-CoV-2 - Yuesheng Wang; Shuying Zhang; Jingyu Chen; Ge Qin; Qiongwen Zhang; Yuxi Liu; Dan Yue; Fanting Wang; Shan Wei; Di Wu; Wenqiao Zang; Li-e Liu; et al. (Chemical Engineering Journal, 2026)

Transcriptomic and proteomic insights into the molecular mechanism underlying cell wall biosynthesis in Moso bamboo (Phyllostachys edulis) - Xin Geng; Yilan E; Xiaojing Wang; Yanjing Liu; Bowen Li; Qingyu Jin; Yuzhen Chen; Cunfu Lu (Plant Cell Reports, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Coupling effect of urban building clusters and crosswinds on the aerodynamic performance of high-speed maglev trains - Jianfeng Mao; Xi Wang; Yikang Liu; Zhiwu Yu; Zheng Li; E Deng (Sustainable Cities and Society, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Quantitative microbiological risk assessment of Shiga toxin-producing Escherichia coli contamination for the beef steak supply chain in China - Xueqing Jiang; Yimin Zhang; George-John E. Nychas; Lixian Zhu; Yunge Liu; Rongrong Liang; Xiaoyin Yang; Ke Li; Pengcheng Dong (International Journal of Food Microbiology, 2026)

W/O/W emulsion-filled egg white gel co-stabilized by protein and γ-cyclodextrin MOFs with multi-chamber encapsulation potential - Chan Li; Xue Yang; Yunfei Zou; Li Zhang; Chuhuan Wei; Yan Ran; E Zhao; Jibiao Yuan; Keshan Wang; Yongguo Jin; Ying Zhou; Qiujin Zhu; et al. (Food Research International, 2026)

Biomagnification of persistent organic pollutants from diets and microplastics to a seabird species (Sula sula) - Ruifeng Lu; Xiaobo Zheng; Lei Li; Yiye Jiang; Jian Guo; Yin-E Liu; Bixian Mai (Environmental Pollution, 2026)

“Global significant trends and countermeasures pertaining to climate change adaptation: Translating ambition into action post-COP29” - Shuo Liu; Yu-E. Li; Qin Ouyang (Environmental Science & Policy, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Integrating crowdsourced geospatial intelligence and urban morphology for urban waterlogging risk mapping in Karachi, Pakistan - Shan-e-hyder Soomro; Huaibin Wei; Muhammad Waseem Boota; Mairaj Hyder Alias Aamir Soomro; Caihong Hu; Yinghai Li; Chengshuai Liu; Junaid Abdul Wahid; Jiali Guo; Xiaotao Shi; Gul-e-Zehra Soomro (Climatic Change, 2026)

The occurrence of extreme heat events offset CO2 fertilization and deteriorate grain quality in double cropping rice systems under projected climate change - Huan Liu; Bin Wang; Yu’e Li; Lu Sun; Longlong Xia; Kees Jan van Groenigen; Yunfan Wan; Tiantian Miao; Weilu Wang; Diego Abalos; Lewis H. Ziska (Agricultural and Forest Meteorology, 2026)

The naked mole-rat cGAS promotes homologous recombination repair and delays aging - Chenxi Du; Yuying Xie; Haolin Ding; Taoxia E; Linpeng Li; Xingguo Liu (Science Bulletin, 2026)

Speciated emissions of full-volatility organic compounds from plastic manufacturing: atmospheric impacts and toxicity generation - Dongyang Wu; Qing’e Sha; Luyun Liu; Citao Zhang; Shan Jiang; Qing Guo; Junhao Xu; Jialin Song; Renjun Li; Liufen Cai; Haoqi Chen; Guanghui Li; et al. (Journal of Environmental Sciences, 2026)

Tris(2,4-di-tert-butylphenyl) phosphate induces cardiac injury in juvenile mice by disrupting energy homeostasis: Focus on mitochondrial impairment - Xiangxiang Chen; Yanan Xia; Lihua Feng; Haoneng Li; Yang'e Li; Shixiang Huang; Hengyi Xu; Yang Liu (Chemico-Biological Interactions, 2026)

The hydroxyl content of biochar mediates the coating structure to dominate the release performance of castor oil-based polyurethane coated urea - Zexi Li; Yufeng Chen; Ruhong Qin; Qianqian Dai; Chunxia Ding; A-juan Zhao; Xiangrong Liu; Fangfang Wu; Mei-e Zhong (Environmental Research, 2026)

Joint Influence of Seed Dormancy and Dispersal Syndrome on Dispersal Distance and Range Size Across Two Climate Regions - Wang Cai; Yuan Liu; YunAo Li; Min Cao; Carol C. Baskin; Jerry M. Baskin; Adriana Alzate; Renske E. Onstein; Jie Yang (Global Ecology and Biogeography, 2026)
Aim Long distance dispersal and the ability to delay germination under unfavourable conditions (dormancy) are critical for plant persistence and range expansion. However, how dispersal syndrome and dormancy interactively shape maximum dispersal distance and species range size across climate regions remains unclear. We tested the hypothesis that a trade‐off between dormancy and dispersal distance operates differently in animal‐mediated versus abiotic dispersal systems, and that climate modulates their influence on range size. Location Global. Time Period Current. Major Taxa Studied Seed plants. Methods We compiled data on dormancy, dispersal syndrome, maximum seed dispersal distance and range size for 631 plant species across 118 families worldwide. We used linear mixed effects models to examine how dormancy and dispersal syndromes interactively shape seed dispersal distance and range size across tropical and temperate regions. Results Non‐dormant species had larger maximum dispersal distances than dormant species, but only in abiotic dispersal systems, consistent with a trade‐off between dispersal and persistence traits (dormancy). In contrast, animal‐mediated dispersal led to larger dispersal distances than abiotic dispersal, regardless of whether species were dormant or not. The influence of dormancy and dispersal syndrome on range size was climate‐dependent. In tropical regions, animal‐mediated dispersal enhanced range size, while dormancy had little effect. In temperate regions, maximum seed dispersal distance was positively associated with range size, but neither dormancy nor animal‐mediated dispersal significantly affected range size. Main Conclusions The interplay between seed dormancy and dispersal syndromes shapes seed dispersal distance and species range size in climate‐specific ways. Animal‐mediated dispersal promotes larger maximum dispersal distances and larger range sizes in tropical regions. In contrast, in abiotic dispersal systems, dormancy leads to relatively small dispersal distances, but dormancy itself does not affect range sizes in temperate or tropical regions. Understanding dispersal‐dormancy dynamics is essential for predicting how plants will respond to environmental changes.

Priorities for enhancing resilience of SDG causal network from a human-nature perspective - Yiming Su; Guangjin Zhou; Mingyuan Wang; Xiaoyun Li; Tao Liang; Lingqing Wang; Jian Hu; Jixi Gao; Wenwu Zhao; Siyuan Tao; Peter E. Holm; Jörg Rinklebe; et al. (Resources, Conservation and Recycling, 2026)

A new method for planning long-distance trails using wilderness quality mapping and trajectory data: A case study of the Taihang Mountain National Forest Trail in China - Yunmiao Chen; Yue Cao; Zhangqian Ye; Tao Liu; Pei Wang; Yunshuang Feng; Lingyun Liao; Mingyang Lv; Zhicong Zhao; Alan E. Watson; Steve Carver; Changjia Li; et al. (Journal of Environmental Management, 2026)

Establishment of an efficient cotyledon-based regeneration system in Juglans sigillata dode - Xiaojin Liu; Chunxiang Li; Wenlong Zhang; Jian Peng; Xuejun Pan; Wen’e Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Synergistic importance of memory and spatial neighbourhood effects in modelling net ecosystem productivity - Jian Liu; Tao Zhou; Jingyu Zeng; Jingzhou Zhang; Xuemei Wu; Yajie Zhang; Qi Zhang; Yancheng Qu; Peixia Liu; Wenjuan Zhang; E Tan; Ying Yu; et al. (Agricultural and Forest Meteorology, 2026)

Proceedings of the 2024 FDA-CRCG Workshop: Scientific and Regulatory Considerations for Assessment of Immunogenicity Risk for Generic Peptide and Oligonucleotide Drug Products - Jennifer K. Lee; Ha-Na Lee; Sudhir Agrawal; Joseph A. Balsamo; Andrew Clerman; Sofie Denies; Anne De Groot; Jeremy Fry; Nicolas Gaudenzio; Andrew J. Graves; Kristina E. Howard; SuJin Hwang; et al. (The AAPS Journal, 2026)

Shifts in microorganisms lead to double peaks in manure-induced temperature sensitivity of soil organic carbon degradation with incubation time - Xiaodong Sun; Yikang Xue; Yu'e Li; Kailou Liu; Wenju Zhang; Minggang Xu; Andong Cai (Soil and Tillage Research, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Nonnegligible migration of rubber-derived chemicals from road surface to adjacent greenbelt soil - Zhen-Yu Ge; Hai-Yan Zhang; Xue-E Li; Yue-Hong Liu; Li-Ni Wei; Xiang-Ning Liang; Yan-Feng Lv; Tuan-Tuan Wang; Sai Wang; Jian-Liang Zhao (Journal of Hazardous Materials, 2026)

Deep eutectic solvents-synergistic ultrasonic-assisted extraction of polyphenols from flaxseed (Linum usitatissimum L.) meal: Optimization, mechanisms, in vitro activity, and structural characterization - Zhanglian Chen; Shiyong Li; Zhilin Zhou; Jiaqi Zhao; Yuxin Fu; Xiaoman Qin; E-yu Ma; Xinyi Jiang; Wenyu Liu; Hongbin Wu; Yi Xu; Changqing Wei (Food Research International, 2026)

Isothiazolinone biocide aggravate disinfection-resistant bacterial fouling on reverse osmosis membranes - Yu-Qing Xu; Zheng-Yang Huo; Yuan Bai; Yun Wang; Wen-Long Wang; Hao-Bin Wang; Yu-Jia Gao; Rui-Ning Wang; Chen-Yu Li; Han Liu; Wei E. Huang; Hong-Ying Hu; et al. (Desalination, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Development of a high-throughput LLE-UPLC-QqQ-MS/MS method and comprehensive profiling of urinary steroid hormones in Chinese elderly adults - Xiao Ma; Huimin Ren; Li Zhao; Xiaojie Guo; Jiran Zhang; Juan Liu; Xiaona Wang; Mengyao Wang; Yifu Lu; Shilu Tong; Hongyang Cui; Hong Chang; et al. (Analytica Chimica Acta, 2026)

Ocean Heat Content Sets Another Record in 2025 - Yuying Pan; Lijing Cheng; John Abraham; Kevin E. Trenberth; James Reagan; Juan Du; Zhankun Wang; Andrea Storto; Karina Von Schuckmann; Yujing Zhu; Michael E. Mann; Jiang Zhu; et al. (Advances in Atmospheric Sciences, 2026)
Global ocean warming continued unabated in 2025 in response to increased greenhouse gas concentrations and recent reductions in sulfate aerosols, reflecting the long-term accumulation of heat within the climate system, with conditions evolving toward La Niña during the year. In 2025, global upper 2000 m ocean heat content (OHC) increased by ∼23 ± 8 ZJ relative to 2024 according to IAP/CAS estimates. CIGAR-RT, and Copernicus Marine data confirm the continued ocean heat gain. Regionally, about 33% of the global ocean area ranked among its historical (1958–2025) top three warmest conditions, while about 57% fell within the top five, including the tropical and South Atlantic Ocean, Mediterranean Sea, North Indian Ocean, and Southern Oceans, underscoring the broad ocean warming across basins. Multiple datasets consistently indicate ocean warming, as measured by 0–2000 m OHC, increased from 0.14 ± 0.03 W m −2 (10 yr) −1 during 1960–2025 to 0.32 ± 0.14 W m −2 (10 yr) −1 during 2005–2025 (IAP/CAS), the latter being consistent with EEI (Earth’s Energy Imbalance) estimates within uncertainties. In contrast, the global annual mean sea surface temperature (SST) in 2025 was 0.49°C above the 1981–2010 baseline and 0.12 ± 0.03°C lower than in 2024 (IAP/CAS; similar in CMA-SST, FY3 MWRI SST, ERSSTv5 and Copernicus Marine data), consistent with the development of La Niña conditions, but still ranking as the third-warmest year on record.

Identification of an allotetraploid hybrid (Pengze crucian carp (♀) × Xingguo red carp (♂)) and its transcriptomic responses to herpesvirus infection - Shujia Liao; Yingshi Tang; Han Wen; Honghai Liang; Guanghong Song; Jingfeng Liu; Mingqing Zhang; Zixuan E; Danqi Lu; Haoran Lin; Shuisheng Li; Yong Zhang (Aquaculture, 2026)

Monoculm1 confers cold tolerance at the seedling stage in rice - Ruiqing Li; Chenfan Zheng; Binqiang Wang; Shang Dai; Yue Song; Huali Zhang; Zhiguo E; Bo Liu; Jiale Chen; Can Zhang; Haowei Fu; Ning Xu; et al. (Molecular Plant, 2026)

Mono(2-ethylhexyl) phthalate activates JNK signaling via TLR4-MD2 binding to induce podocyte injury in chronic kidney disease - Jiajun Jing; Shaohui Liu; Li Yan; Li'e Zhang; Qiuju Liang; Yuting Wen; Xiaofeng Huang; Zijuan Qi; Mingjun Wang; Zi'ang Huang; Sijin Liu; Yunfeng Zou; et al. (Journal of Hazardous Materials, 2026)

Flavor modulation of braised He Bao carp (Cyprinus carpio) by natural plant spices: Insights from GC–MS, GC–IMS, E-nose, E-tongue, and molecular docking analyses - Yuwei Liu; Yuting Wang; Ziyi Liu; Chang Li; Qiang Yu; Jianhua Xie; You Long; Qianzhu E; Yi Chen (Food Bioscience, 2026)

Immunological Characteristics of Triploid Grass Carp (Ctenopharyngodon idella) and evaluation of its phagocytosis in the macrophages of head kidney - Xiaoman Huang; Zixuan E; Hao Yang; Guihong Lai; Shuang Liu; Shujia Liao; Jiaqi Lin; Siyi Liu; Chen Long; Haoran Lin; Danqi Lu; Shuisheng Li; et al. (Fish & Shellfish Immunology, 2026)

Self-supplying glucose/oxygen hydrogel enhances dental pulp stem cell survival and vascularized tissue regeneration through Erk1/2-VEGF signaling - Xinyu Liu; Xiaofan Liu; Yuping Zhao; Yang Liu; Huimin Wang; Yi Li; Nan Ma; Hongchen Sun; Fermín E. González; Youliang Zhu; Junfeng Zhou; Yuewei Zhang; et al. (Chemical Engineering Journal, 2026)

Ti3C2-Cl-Bi12O17Cl2/Bi12O17Cl2 Mott-Schottky heterojunction with mixed noncovalent/covalent type to boost ultra-sensitive photoelectrochemical sensing of ciprofloxacin - Chu-Chu Hu; Qi-E Zhang; Shao-Peng Shi; Guo-Qing Zhao; Yan-Sha Gao; Ping Liu; Xun-Kuan Ye; Yan Pan; Hui-Qing Lv; Li-Min Lu (Chemical Engineering Journal, 2026)

Advancing high-resolution hourly PM2.5 forecasting with a hybrid framework integrating numerical simulation and machine learning - Yuan Liu; Zizheng Li; Pablo E. Saide; Ming Zhang; Qingqing He (Atmospheric Research, 2026)

A decision support tool for rubble stabilization on coral reefs - Shu Kiu Leung; Tania M. Kenyon; Laurie J. Raymundo; Helen E. Fox; Nathan Cook; Kailash Cook; Alasdair J. Edwards; Eric E. Fisher; Arnaud J.T. Brival; Freda E. Nicholson; Robin W.L. Philippo; Andrew C.F. Taylor; et al. (Journal of Environmental Management, 2025)

Dynamic changes in physicochemical properties, flavor, and microbial communities during kombucha fermentation with dominant autochthonous strains inoculation - E. Liao; Na Liu; Qian Li; Han Li; Lu Wang; Wenmin Wu (Food Research International, 2025)

Emission characteristics of full-volatility organic compounds from China's aluminum-products industry and their impacts on secondary organic aerosol and ozone potentials - Dongyang Wu; Qing'e Sha; Shan Jiang; Luyun Liu; Citao Zhang; Jialin Song; Junhao Xu; Haoqi Chen; Guanghui Li; Zhangmin Xiang; Bin Jiang; Zhuangmin Zhong; et al. (Environmental Research, 2025)

C/N-Driven Synergies: Earthworms optimize CO2/N2O mitigation and soil quality in floral waste recycling - Hongyang Li; Guijun Wu; Mei Li; Changqun Duan; Chang-e Liu (Environmental Research, 2025)

Simulation of carbon fluxes from Tibetan Plateau grasslands by integrating data assimilation and parameter inversion within the Biome-BGC model - Jingzhou Zhang; Tao Zhou; Li Cao; Jingyu Zeng; Yajie Zhang; Qi Zhang; Xuemei Wu; Yancheng Qu; E. Tan; Xia Liu (Ecological Modelling, 2025)

Modulating charge separation in g-C3N4 via synergistic carbon self-doping and nitrogen defects engineering for enhanced photocatalytic H2 evolution and CO2 reduction - Samuel Guemou; Fazal E. Haq; Cheng Cheng; Huaiwu Peng; Kang Chen; Yu Chen; Xin Li; Maochang Liu; Jinwen Shi (Chemical Engineering Journal, 2025)

The fate of multiple antibiotics in a counter-diffusion biofilm system carrying out short-cut nitrification and denitrification when treating saline wastewater - Ting Li; Mingxuan Lyu; Boyang Hu; Yi Li; Yuan Zhang; Hao Liu; Baoan Li; Bruce E. Rittmann (Chemical Engineering Journal, 2025)

Palaeoecological reconstruction of shoreline terrestrialisation of Lake Glubokoe (Smolensk-Moscow Upland) in the late Holocene based on the results of a multi-proxy analysis - Yulia A. Pastukhova; Andrey N. Tsyganov; Natalia G. Mazei; Elena E. Severova; Dmitrii O. Sadokov; Viktor A. Chernyshov; Ekaterina V. Tkacheva; Jinyue Li; Yanwei Liu; Alexey A. Kotov; Andrey V. Kitashov; Ping Ding; et al. (Journal of Paleolimnology, 2025)

Prof Stephen P. Long, FRS (1950–2025) - Lorenzo Álvarez‐Filip; Edith Bai; Carl J. Bernacchi; Rhea Bruno; Klaus Butterbach‐Bahl; Maria Byrne; I‐Ching Chen; Shaolin Chen; William W. L. Cheung; M. Francesca Cotrufo; Tatenda Dalu; Xiaojuan Feng; et al. (Global Change Biology, 2025)

High Quality, Granular, Timely, Trustworthy and Efficient Vertebrate Species Distribution Data Across a 30,000 km 2 Protected Area Complex - Yinqiu Ji; Alex Diana; Xueyou Li; Eleni Matechou; Jim E. Griffin; Shuwei Liu; Mingjie Luo; Chunying Wu; Ru Bai; Chenyang Yao; Tingting Yin; Feng Dong; et al. (Ecology Letters, 2025)
The routine generation of species distribution data at scale remains a challenge. We used aquatic environmental DNA metabarcoding to sample vertebrate species across the 30,000 km 2 Gaoligongshan region along the China–Myanmar border. In just 56 calendar days (33 researcher‐field‐days + 69 researcher‐lab‐days), we detected 389 vertebrate species, of which 35 are Red‐Listed. We introduce the ‘eDNA‐aware’ OccPlus occupancy model, which accounts for false‐negative and false‐positive error in the field and lab. OccPlus leverages the taxonomic breadth of eDNA datasets by using ordination to estimate species occupancies. We recover known biogeographic patterns and find that native terrestrial and fish species have higher occupancies inside protected areas while domesticated species and non‐native fishes have higher occupancies outside them. Our study demonstrates how eDNA metabarcoding can obtain high‐quality, granular, timely, trustworthy and efficient species distribution data to facilitate nature conservation and restoration.

The role of protein post-translational modifications and their crosstalk in determining pluripotent stem cells fate - Wenhui Fan; Taoxia E; Bin Lu; Hongyan Sun; Keshi Chen; Xingguo Liu; Linpeng Li (Science Bulletin, 2025)

Metabolomics combined with 16S rDNA revealed the effects of low protein diet on rumen microbiome structure, nitrogen utilization rate and differential metabolites in feces and urine of dairy cows - Yaqiong Ren; Caijuan Yue; Wenzhuo Wang; Li Cai; Yanming Wang; Xiaojing Liu; Depeng Li; Qiao'’e Zhang (Research in Veterinary Science, 2025)

Dual-strategy stabilization of zinc anodes through solvation regulation and interfacial engineering in aqueous zinc ion batteries - Weilin Yan; Yifan Wang; Lufan Liu; Feiyu Tao; Yang Huang; Zhaoqian Li; Li'e Mo; Hong Zhang; Linhua Hu (Chemical Engineering Journal, 2025)

Differential effects of Ca2+ and Mn2+ on cyanobacterial mineralization and organic matter preservation - Jie Li; Yongjie Zhang; Yanyang Zhao; Chao Han; Kaiming Hu; Wenhui Chen; Yangmei Fei; Yongmei Liu; Haoran Li; Maurice E. Tucker; Zuozhen Han (Chemical Geology, 2025)

Bio-organic fertilizer amendment helps suppress tomato bacterial wilt disease by improving aggregation and enhancing the pathogen inhibition capacity within micro-aggregates - Menghui Dong; Eiko E. Kuramae; Mengli Zhao; Yi Min; Shanshan Liu; Xu Xu; Qirong Shen; Rong Li; George A. Kowalchuk (Biology and Fertility of Soils, 2025)

Mycorrhizal allies: synergizing forest carbon and multifunctional restoration - Tengteng Li; Richard P. Phillips; Matthias C. Rillig; Gerrit Angst; E. Toby Kiers; Paola Bonfante; Nico Eisenhauer; Zhanfeng Liu (Trends in Ecology & Evolution, 2025)

NH3, N2O, NO and NO2 losses, emission factors and reduction mechanisms under different N managements from greenhouse vegetable soils - Tiantian Miao; Bin Wang; Yunfan Wan; Yu'e Li; Tianjing Ren; Huan Liu; Jiaqi Zhang; Andong Cai; Waseem Hassan (Journal of Environmental Management, 2025)

Cadmium stress drives remodeling of earthworm mucus metabolism: Hormetic antioxidant response and synergistic amino acid defence mechanisms - Guijun Wu; Changqun Duan; Hongyang Li; Mei Li; Chang-e Liu (Environmental Research, 2025)

Efficient Hg(II) removal using recyclable poly(thioctic acid)/SH-UiO-66 functionalized polyacrylonitrile fiber: Multifunctional binding strategy - Ningge Jian; Gaoran Zhang; Hongli Liu; Di Wu; Jia Wang; Yuxin Wang; Yi Cheng; Qingyuan Liu; Yongjun Wu; Li-e Liu (Chemical Engineering Journal, 2025)

Multi-electron donation promotes the photocatalytic conversion of carbon dioxide to methane in a covalent bonded metal-complex/quantum dots hybrid catalyst - Qian Zhao; Mohamed Abdellah; Yang Liu; Jie Meng; Xianshao Zou; Kasper Enemark-Rasmussen; Yu Zhou; Yi Li; Yuehan Cao; Yijiang Chen; Nora Eliasson; Ying Zhou; et al. (Chemical Engineering Journal, 2025)

Reestablished buried interface by multifunctional additive for high-efficiency perovskite solar cells - Xiaoli Zhang; Fobao Xie; Bing’e Li; Xinghan Zeng; Chuangping Liu; Qinghua Cao; Jiangping Xing; Eugene Troyan; Baihong Zheng; Hui Liu; Andrey Stepanov (Chemical Engineering Journal, 2025)

Recognition of novel metal-resistant microbes and their potential resistance mechanisms in metal mines - Ting Li; Chang'e Liu; Chenyang Zhang; Changqun Duan (Applied Soil Ecology, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Magnetite-augmented sulfur-siderite autotrophic denitrification: Deep nitrogen removal at ultra-low HRT from lab to pilot scale - Jiale Sun; Haoyong Li; He Dong; Lu Liu; Chunyv Zhou; Ziwen Du; Yan Dang; Dawn E. Holmes (Water Research, 2025)

Nitrogen fixation in Pampinifervens, a new species-rich genus of Aquificaceae that inhabits a wide pH range in terrestrial hot springs - Marike Palmer; Nancy O. Nou; Lara A. Turello; Carolyn E. Power; John C. Ong; Jonathan K. Covington; Dengxun Lai; Xavier Mayali; Anna-Louise Reysenbach; Yan-Ling Qi; Jeremy A. Dodsworth; Jian-Yu Jiao; et al. (Systematic and Applied Microbiology, 2025)

Petrogenesis of the olivine cumulate outcrop Issole – The missing link between the Séítah and Máaz formations in Jezero crater, Mars - Juan David Hernández-Montenegro; Tanya V. Kizovski; Allan H. Treiman; An Y. Li; Paul D. Asimow; Mariek E. Schmidt; Yang Liu; Josh Labrie; Abigail L. Knight; Michael M. Tice; David A. Klevang; Scott VanBommel; et al. (Icarus, 2025)

Simultaneous N-methyl pyrrolidone and total-nitrogen removals in a single aerobic process - Fei Liu; Meng Huang; Chenyu Li; Linlin Chen; Yongming Zhang; Bruce E. Rittmann (International Biodeterioration & Biodegradation, 2025)

Millet stable isotopes reveal the advance of agricultural practices in the core political regions of early imperial China - Jingwen Liao; Edward Allen; Amanda G. Henry; Jason E. Laffoon; Ming Li; Daiyun Liu; Pengfei Sheng (CATENA, 2025)

Remobilization of Ni in framboidal pyrite within sulfide nodules in Early Cambrian nickeliferous black shales - Xu-Yang Liu; Ya-Fei Wu; Daniel D. Gregory; Katy Evans; Anthony E. Williams-Jones; Wen Zhang; Mei-Fu Zhou; Jian-Wei Li (Chemical Geology, 2025)

JsSAMDC promotes polyamine synthesis and flowering genes to synergistically regulate female flower bud differentiation - Jinyan Chen; Wenwen Li; Chunxiang Li; Yuanqi Huang; Jian Peng; Dong Huang; Mengmeng Liu; Xuejun Pan; Wen’ e Zhang (Plant Cell Reports, 2025)

Air quality and mental health amid COVID-19: a prospective population-based analysis of the mediating role of daily routine disruptions - Selina Kit Yi Chan; Crystal Jingru Li; Percy Poo-see Tse; Evon Lam Wong; Anan Wang; Huinan Liu; Stevan E. Hobfoll; Chi Yung Jim; Wai Kai Hou (Air Quality, Atmosphere & Health, 2025)

Enhanced sulfamethoxazole (SMX) degradation by Shewanella oneidensis MR-1 via a microbially driven Fenton reaction - Qing-Jiahui Fan; Wei Li; Gen-Ji Yao; Zu-Hao Wang; Han Fu; Yong-Di Liu; Bruce E. Rittmann (Journal of Water Process Engineering, 2025)

Enhancing ecological risk assessment of dioxins in aquatic environments: AHR diversity and species sensitivity differences in tiger puffer (Takifugu rubripes) - Zhenhong Xue; Wanglong Zhang; Anran Ren; Sibel I. Karchner; Diana G. Franks; Yanjiao Zong; Yongchao Ma; Jiayi Wang; Yiqin Xu; Jiaming Li; Ning Ding; Chunchen Liu; et al. (Journal of Hazardous Materials, 2025)

Quality changes in the physiology, behaviour, nutrition, and taste of Urechis unicinctus during waterless live transportation - Teng Teng; Yuchun Lu; Zichen Deng; Shuqi Wang; Yuting Yang; Huihong Li; Chun-E Liu (Food Chemistry, 2025)

Early life phthalate exposure impacts gray matter and white matter volume in infants and young children - Emily J. Werder; Kun Lu; Chih-Wei Liu; Jake E. Thistle; Julia E. Rager; Gang Li; Zhengwang Wu; Tengfei Li; Li Wang; Dale P. Sandler; John H. Gilmore; Joseph Piven; et al. (Environmental Research, 2025)

Sociodemographic, medical, health behavior, and psychosocial factors associated with COVID-19 diagnoses in the New Jersey cancer survivor cohort - Sharon Manne; Adana A. M. Llanos; Hari S. Iyer; Lisa E. Paddock; Katie Devine; Shawna V. Hudson; Denalee O’Malley; Elisa V. Bandera; Sara Frederick; Jacintha Peram; Justin Solleder; Shengguo Li; et al. (Cancer Causes & Control, 2025)
Background Cancer survivors are more susceptible to contracting COVID-19. However, beyond race, age, and sex, less is known about other neighborhood and psychosocial factors contribute to this increased risk. Objective The goal of this study was to examine the associations of individual and area-level social determinants of health (SDOH) measures, medical, lifestyle, and psychosocial factors and COVID-19 infection in a statewide cohort of cancer survivors in New Jersey. Methods Survey data from 864 cancer survivors in New Jersey were collected from 2018 to 2022, which were merged with study participant data from the state of New Jersey on COVID-19 diagnoses in 2020, 2021, and 2022. We estimated adjusted odds ratios (aOR) for associations of COVID-19 diagnosis with individual-level factors (cancer type and stage, health behaviors, and psychosocial factors) and area-level SDOH [Social Vulnerability Index, Area Deprivation Index, and Index of Concentration at the Extremes (ICE) to quantify racialized deprivation vs. privilege based on income]. Results Cancer survivors born outside the US were more than twice as likely to contract COVID-19 compared to US-born survivors (aOR 2.29, 95% CI 1.01, 4.92). Compared to Quartile 4, residence in an area in Quartile 1 of racialized income ICE (i.e., predominantly Black, low income) was associated with higher odds of COVID-19 (aOR 2.15, 95% CI 0.98, 4.87). Retired survivors had lower odds of COVID-19 (aOR 0.39, 95% CI 0.19, 0.80) compared to those who were employed. Higher social well-being was associated with higher COVID-19 (aOR 1.07, 95% CI 1.02, 1.13). Type of cancer and cancer treatments received were not associated with the risk of COVID-19. Conclusions Immigrant status and increased racialized deprivation as measured by ICE for income were associated with COVID-19. These findings support evidence that individual and area-level SDOH measures contribute to increased risk of COVID-19 among cancer survivors.

On the long and winding road: unravelling the late emergence of Neolithic agriculture in the Nile Delta - Xiaoshuang Zhao; David Kaniewski; Yanna Wang; Nick Marriner; Alaa Salem; Said E. Alassal; Yan Liu; Feng Jiang; Jing Chen; Qianli Sun; Maotian Li; Ian Thomas; et al. (Quaternary Science Reviews, 2025)

Clinical biomarkers of perioperative neurocognitive disorder: initiation and recommendation - Jianhui Liu; Cheng Li; Junyan Yao; Lei Zhang; Xuan Zhao; Xin Lv; Zhiqiang Liu; Changhong Miao; Yingwei Wang; Hong Jiang; Weifeng Yu; Tianlong Wang; et al. (Science China Life Sciences, 2025)

Characteristics and evolution of mass-transport complex since Late Miocene in the Zengmu and Beikang basins, southern South China Sea - Shuqin Huang; Ming Su; Haiteng Zhuo; Li Zhang; Shan Liu; Zhi Lin Ng; Zhixuan Lin; Boda Zhang; Kunwen Luo; Li’e Lin (Journal of Oceanology and Limnology, 2025)

Behavioral Responses of Migratory Fish to Environmental Cues: Evidence from the Heishui River - Jiawei Xu; Yilin Jiao; Shan-e-hyder Soomro; Xiaozhang Hu; Dongqing Li; Jianping Wang; Bingjun Liu; Chenyu Lin; Senfan Ke; Yujiao Wu; Xiaotao Shi (Fishes, 2025)
Hydropower infrastructure has profoundly altered riverine connectivity, posing challenges to the migratory behavior of aquatic species. This study examined the post-passage migration efficiency of Schizothorax wangchiachii in a regulated river system, focusing on upstream and downstream reaches of the Songxin Hydropower Station on the Heishui River, a tributary of the Jinsha River. We used radio-frequency identification (RFID) tagging to track individuals after fishway passage and coupled this with environmental monitoring data. A Cox proportional hazards model was applied to identify key abiotic drivers of migration success and to develop a predictive framework. The upstream success rate was notably low (15.6%), with a mean passage time of 438 h, while downstream success reached 81.1%, with an average of 142 h. Fish exhibited distinct diel migration patterns; upstream movements were largely nocturnal, whereas downstream migration mainly occurred during daylight. Water temperature (HR = 0.535, p = 0.028), discharge (HR = 0.801, p = 0.050), water level (HR = 0.922, p = 0.040), and diel timing (HR = 0.445, p = 0.088) emerged as significant factors shaping the upstream movement. Our findings highlight that fishways alone may not ensure functional connectivity restoration. Instead, coordinated habitat interventions in upstream tributaries, alongside improved passage infrastructure, are crucial. A combined telemetry and modeling approach offers valuable insights for river management in fragmented systems.

Biotic and abiotic drivers of soil carbon, nitrogen and phosphorus and metal dynamic changes during spontaneous restoration of Pb–Zn mining wastelands - Sichen Wang; Ting Li; Xinqi Yuan; Ji Yu; Zhifei Luan; Zhaolai Guo; Yadong Yu; Chang’e Liu; Changqun Duan (Journal of Hazardous Materials, 2025)

Record High Temperatures in the Ocean in 2024 - Lijing Cheng; John Abraham; Kevin E. Trenberth; James Reagan; Huai-Min Zhang; Andrea Storto; Karina Von Schuckmann; Yuying Pan; Yujing Zhu; Michael E. Mann; Jiang Zhu; Fan Wang; et al. (Advances in Atmospheric Sciences, 2025)
Heating in the ocean has continued in 2024 in response to increased greenhouse gas concentrations in the atmosphere, despite the transition from an El Niño to neutral conditions. In 2024, both global sea surface temperature (SST) and upper 2000 m ocean heat content (OHC) reached unprecedented highs in the historical record. The 0–2000 m OHC in 2024 exceeded that of 2023 by 16 ± 8 ZJ (1 Zetta Joules = 10 21 Joules, with a 95% confidence interval) (IAP/CAS data), which is confirmed by two other data products: 18 ± 7 ZJ (CIGAR-RT reanalysis data) and 40 ± 31 ZJ (Copernicus Marine data, updated to November 2024). The Indian Ocean, tropical Atlantic, Mediterranean Sea, North Atlantic, North Pacific, and Southern Ocean also experienced record-high OHC values in 2024. The global SST continued its record-high values from 2023 into the first half of 2024, and declined slightly in the second half of 2024, resulting in an annual mean of 0.61°C ± 0.02°C (IAP/CAS data) above the 1981–2010 baseline, slightly higher than the 2023 annual-mean value (by 0.07°C ± 0.02°C for IAP/CAS, 0.05°C ± 0.02°C for NOAA/NCEI, and 0.06°C ± 0.11°C for Copernicus Marine). The record-high values of 2024 SST and OHC continue to indicate unabated trends of global heating.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

The molecular mechanism of electrical stimulation on enhancing the foaming properties of egg white liquid - E. Zhao; Chan Li; Jing Yuan; Keshan Wang; Jingchun Ma; Ying Zhou; Qiujin Zhu; Xiaoli Liu; Yongguo Jin; Yuanyuan Liu (Food Hydrocolloids, 2025)

Dual-interface induced bandgap regulated water-based flexible interactive generator - Ye Zhou; Pengcheng Wu; Yuchang Zhu; Huoerhute Yelemulati; Shanshan Zhu; Keliang Wu; Guihua Meng; Hao Wang; Fathy Hassan; Mohsen Sherif; Guanglin Li; Zhiyong Liu; et al. (Chemical Engineering Journal, 2025)

Linking soil extracellular enzymes with soil respiration under altered litter inputs - Hao Chen; Qianhao Xu; Kees Jan van Groenigen; Bruce A. Hungate; Pete Smith; Dejun Li; Daryl L. Moorhead; Brooke B. Osborne; Zilong Ma; Jørgen E. Olesen; Chaoqun Wang; Ji Liu; et al. (Agricultural and Forest Meteorology, 2025)

Global Patterns of Climatic Niche Evolution in Angiosperms - Yunpeng Liu; John J. Wiens; Ao Luo; Xiaoting Xu; Dimitar Dimitrov; Xiangyan Su; Yichao Li; Tong Lyu; Loic Pellissier; Niklaus E. Zimmermann; Douglas E. Soltis; Pamela S. Soltis; et al. (Global Ecology and Biogeography, 2025)
Aim A species' rate of climatic niche evolution may reflect its ability to survive changing climates. Yet large‐scale studies of these rates remain limited. Here, we assessed global patterns in climatic niche rates among angiosperms and explored the potential drivers shaping these patterns. Location Global. Time Period Current. Major Taxa Studied Angiosperms. Methods We estimated broad‐scale climatic niches for 231,567 angiosperm species based on distributional data from over 1100 sources. By integrating a published phylogeny of angiosperms, we estimated rates of climatic niche change for each extant species as the difference between its current and ancestral niche divided by the species' age. Global patterns were analysed by averaging rates for all the species found in each geographic unit. We used multiple statistical models to explore the relative contributions of niche width and climatic seasonality to shaping these geographic patterns of niche evolution. We analysed patterns of niche evolution and their underlying drivers separately for temperature‐related and precipitation‐related niches and for different directions of niche evolution (i.e., increases and decreases in species' temperature and precipitation niche values when compared to their most recent ancestors). Results Rates for temperature variables increased with latitude, whereas rates for precipitation variables decreased with latitude. These opposing patterns in temperature and precipitation rates were related to opposing latitudinal patterns in climatic seasonality and species' niche widths for temperature and precipitation. Rates also differed for different directions of niche evolution, with different patterns associated with changes to warmer vs. cooler climates and wetter vs. drier climates. Main Conclusions Our results revealed large‐scale geographic patterns in rates of climatic niche change for temperature and precipitation for the largest clade of angiosperms and their underlying drivers. These findings may have important implications for species' abilities to respond to recent climate change.

Exosomes secreted from M2-polarized macrophages inhibit osteoclast differentiation via CYLD - Zi-yan Guo; Nan-nan Yin; Xiao-fei Li; Meng-meng Wang; Xiao-na Sui; Cai-di Jiang; Ming-hua Xu; Xiao-e Jia; Chong-jian Fu; Tie-lou Chen; Xin Liu (Tissue and Cell, 2025)

An ingenious integrated metal-organic frameworks-based ratiometric sensing platform for efficient, sensitive and real-time detection of tetracyclines - Yueyi Shen; Li-e Liu; Tong Li; Ruili Liu; Jingyi Zhang; Jiaojiao Chen; Xuqing Zhang; Xinyi Li; Ningge Jian; Di Wu (Food Chemistry, 2025)

Enhancing the adsorption capacity of lignin-based super activated carbon for trace toluene under highly humid conditions through [2 + 1] cycloaddition reactions - Zhenrui Li; Haifeng Zuo; Minglei Su; Zhenbing Sun; Jianfeng Ma; Xing’e Liu; Pengyi Zhang (Chemical Engineering Journal, 2025)

Genetic advancements and future directions in ruminant livestock breeding: from reference genomes to multiomics innovations - Songsong Xu; Zhanerke Akhatayeva; Jiaxin Liu; Xueyan Feng; Yi Yu; Bouabid Badaoui; Ali Esmailizadeh; Juha Kantanen; Marcel Amills; Johannes A. Lenstra; Anna M. Johansson; David W. Coltman; et al. (Science China Life Sciences, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Screening of Spinal Muscular Atrophy Carriers and Prenatal Diagnosis in Pregnant Women in Yancheng, China - Huilin Sun; Jianli Zheng; Qing’e Zhang; Feifei Ying; Yadong Fu; Yongjuan Guan; Jing Wu; Yueyun Zhou; Jingjing Dong; Mengjun Xu; Fangfang Yang; Ning An; et al. (Biochemical Genetics, 2025)

Mo4+-Pb2+ redox triggers self-enhanced removal and recovery of Pb2+ with superselectivity - Yang Yu; Yangqi E; Hetao Liu; Qian Li; Huachang Jin; Xueming Chen; Jianmeng Chen; Dongzhi Chen (Water Research, 2025)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

GRANDlib: A simulation pipeline for the Giant Radio Array for Neutrino Detection (GRAND) - R. Alves Batista; A. Benoit-Lévy; T. Bister; M. Bohacova; M. Bustamante; W. Carvalho; Y. Chen; L. Cheng; S. Chiche; J.M. Colley; P. Correa; N. Cucu Laurenciu; et al. (Computer Physics Communications, 2025)

The effect of heatwave and cold spell on cardiovascular disease mortality in central China, 2018–2022 - Ling-Shuang Lv; Li Yin; Yuan Liu; Chun-Liang Zhou; Ji Hu; Ning An; Xian Xie; Xing-E Zhang; Min Zhang; Xiu-Ying Liu (International Journal of Biometeorology, 2025)

Temperature drives reproductive activity in a rare trioecy population of Corbicula clams - Jie Pi; Yangxin Tang; Neil E. Coughlan; Linwei Liu; Xu Wang; Xinhua Liu; Jianguo Xiang; Deliang Li (Hydrobiologia, 2025)

Critical assessment of missense variant effect predictors on disease-relevant variant data - Ruchir Rastogi; Ryan Chung; Sindy Li; Chang Li; Kyoungyeul Lee; Junwoo Woo; Dong-Wook Kim; Changwon Keum; Giulia Babbi; Pier Luigi Martelli; Castrense Savojardo; Rita Casadio; et al. (Human Genetics, 2025)
Regular, systematic, and independent assessments of computational tools that are used to predict the pathogenicity of missense variants are necessary to evaluate their clinical and research utility and guide future improvements. The Critical Assessment of Genome Interpretation (CAGI) conducts the ongoing Annotate-All-Missense (Missense Marathon) challenge, in which missense variant effect predictors (also called variant impact predictors) are evaluated on missense variants added to disease-relevant databases following the prediction submission deadline. Here we assess predictors submitted to the CAGI 6 Annotate-All-Missense challenge, predictors commonly used in clinical genetics, and recently developed deep learning methods. We examine performance across a range of settings relevant for clinical and research applications, focusing on different subsets of the evaluation data as well as high-specificity and high-sensitivity regimes. Our evaluations reveal notable advances in current methods relative to older, well-cited tools in the field. While meta-predictors tend to outperform their constituent individual predictors, several newer individual predictors perform comparably to commonly used meta-predictors. Predictor performance varies between high-specificity and high-sensitivity regimes, highlighting that different methods may be optimal for different use cases. We also characterize two potential sources of bias. Predictors that incorporate allele frequency as a predictive feature tend to have reduced performance when distinguishing pathogenic variants from very rare benign variants, and predictors trained on pathogenicity labels from curated variant databases often inherit gene-level label imbalances. Our findings help illuminate the clinical and research utility of modern missense variant effect predictors and identify potential areas for future development.

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

Contribution of China’s carbon budget on global radiative forcing - Nan Li; Yaoping Cui; Xiaoyan Liu; Zhifang Shi; Mengdi Li; Michael E. Meadows (Journal of Geographical Sciences, 2025)

Bifunctional probe propelling multipath strand displacement amplification tandem CRISPR/Cas12a for ultrasensitive and robust assay of DNA methyltransferase activity - Fei Yu; Qiongwen Zhang; Tiantian Ma; Shuying Zhang; Fanting Wang; Dan Yue; Shihan Liu; Yueqi Liao; Li-e Liu; Yongjun Wu; Wenqiao Zang (Analytica Chimica Acta, 2025)

A study on the runoff prediction mechanism of “water-soil-heat” in cold alpine regions with complex spatial distribution - Qiying Yu; Yungang Bai; Zhenlin Lu; Chengshuai Liu; Shan-e-hyder Soomro; Wenzhong Li; Lu Tian; Yingying Xu; Chen Shi; Biao Cao; Caihong Hu (Science of The Total Environment, 2025)

How Rhodococcus ruber accelerated biodegradation of benzophenone-3 - Fei Liu; Yue Ma; Wenxuan Li; Jue Cai; Haiyun Zhang; Fu Chen; Yongming Zhang; Bruce E. Rittmann (Journal of Hazardous Materials, 2025)

Effects of rumen metabolite butyric acid on bovine skeletal muscle satellite cells proliferation, apoptosis and transcriptional states during myogenic differentiation - Xiao-Wei Wang; Yan-Ling Ding; Cheng-Long Li; Qing Ma; Yuan-Gang Shi; George E Liu; Cong-Jun Li; Xiao-Long Kang (Domestic Animal Endocrinology, 2025)

Novel synthesis of sulfur-doped Ag3PO4 photocatalyst for efficient degradation of cylindrospermopsin - Xu Zhang; Li Zhou; Yiyang Liu; E Hengchao; Zhiyong Zhao; Huaqiang Chu; Xuefei Zhou; Yalei Zhang; Guoyan Zou (Chemical Engineering Journal, 2025)

pH-Responsive lignin-modified copper-based metal-organic frameworks for precision thiamethoxam delivery in the targeted control of red imported fire ants (Solenopsis invicta) - Pengpeng Liu; Amir E. Kaziem; Chen Li; Xin Wang; Shiqi Zhu; Jinzhe Chang; Dongmei Cheng; HanHong Xu; Zhixiang Zhang; Liupeng Yang (Chemical Engineering Journal, 2025)

Influence of land-use type on earthworm diversity and distribution in Yunnan: Insights from soil properties - Chang-E Liu; Qing-Rui Luo; Yan-Lan Xiao; Hong-Yang Li; Hong-Juan Dong; Chang-Qun Duan (Applied Soil Ecology, 2025)

Industrial hemp (Cannabis sativa L.) adapts to cadmium stress by reshaping rhizosphere fungal community - Tingting Feng; Zhuang Meng; Huifen Li; Guohui Chen; Chang'e Liu; Kailei Tang; Jinquan Chen (Science of The Total Environment, 2024)

Cascaded reservoirs promote phosphorus bioavailability of surface sediments in the Upper Mekong River - Zhengjian Yang; QiFeng Min; Xiaojuan Guo; Congfeng Wang; Bi'’e Yan; Xiaoling Li; Defu Liu; Jun Ma; Andreas Lorke (Science of The Total Environment, 2024)

Improvement of soil nutrient cycling by dominant plants in natural restoration of heavy metal polluted areas - Ting Li; Sichen Wang; Luoqi Zhao; Xinqi Yuan; Yuhan Gao; Denggao Fu; Chang'e Liu; Changqun Duan (Environmental Research, 2024)

Biological invasion is eroding the unique assembly of island herpetofauna worldwide - Weishan Tu; Yuanbao Du; Yoel E. Stuart; Yanxia Li; Yanping Wang; Qingfa Wu; Baocheng Guo; Xuan Liu (Biological Conservation, 2024)

Ameliorating the detrimental effects of chromium in wheat by silicon nanoparticles and its enriched biochar - Li Jia; Yue Song; Fangfang You; Sujun Wang; Umm e Rabiya; Xing Liu; Liping Huang; Liye Wang; Waqas ud Din Khan (Science of The Total Environment, 2024)

Recent selection and introgression facilitated high-altitude adaptation in cattle - Yang Lyu; Fuwen Wang; Haijian Cheng; Jing Han; Ruihua Dang; Xiaoting Xia; Hui Wang; Jincheng Zhong; Johannes A. Lenstra; Hucai Zhang; Jianlin Han; David E. MacHugh; et al. (Science Bulletin, 2024)

Dissolved ammonia catalyzes proto-dolomite precipitation at Earth surface temperature - Ruirui Meng; Zuozhen Han; Xiao Gao; Yanyang Zhao; Chao Han; Yu Han; Renchao Yang; Shuangjian Li; Fang Liu; Maurice E. Tucker; Yanjing Chen (Earth and Planetary Science Letters, 2024)

Polyacrylonitrile nanofibrous mat modified with cysteamine and ionic liquid as a recyclable and efficient adsorbent for selective removal of sulfonamides and Cu(II) from aqueous solution: Roles of multi-function adsorption - Hongli Liu; Yuanyuan Dai; Di Wu; Gaoran Zhang; Yongjun Wu; Li-e Liu; Ningge Jian (Chemical Engineering Journal, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Oxygen levels differentially attenuate the structure and diversity of microbial communities in the oceanic oxygen minimal zones - Jiaqian Li; Ningdong Xie; Xiuping Liu; Mohan Bai; Dana E. Hunt; Guangyi Wang (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

From lake to fisheries: Interactive effect of climate and landuse changes hit on lake fish catch? - Shan-e-hyder Soomro; Muhammad Waseem Boota; Haider M. Zwain; Majid Rasta; Caihong Hu; Chengshuai Liu; Yinghai Li; Ao li; Jijun Chen; Chunyun Zhu; Sher Ali; Jiali Guo; et al. (Environmental Research, 2024)

What is the character of N deposition and its proportion to NH3 and NOX inside horticultural greenhouse? - Tiantian Miao; Huan Liu; Yu'e Li; Yunfan Wan; Tianjing Ren; Andong Cai; Bin Wang (Environmental Pollution, 2024)

LLZTO crosslinks form a highly stretchable self-healing network for fast healable all-solid lithium metal batteries - Yingxin Zhang; Xiaohui Yu; Xiaoxiao Li; Jianguo Ren; Peng He; Chao Zhang; Cuiqing Teng; Yue-E Miao; Tianxi Liu (Chemical Engineering Journal, 2024)

Niche similarity accompanying COI genetic differentiations in asexual and sexual Corbicula lineages within East and Southeast Asia - Yangxin Tang; Jie Pi; Neil E. Coughlan; Linwei Liu; Xinhua Liu; Jianguo Xiang; Deliang Li (Hydrobiologia, 2024)

Environmentally-friendly alkaline ionized water pretreatment and hydrolysis of macroalga via microwave-assisted heating to improve monosaccharide yield for bioethanol production - Wei-Hsin Chen; Li-Xuan Liu; Kuan Shiong Khoo; Herng-Kuang Sheen; Eilhann E. Kwon; Ayyadurai Saravanakumar; Jo-Shu Chang (Process Safety and Environmental Protection, 2024)

A fast microbial nitrogen-assimilation technology enhances nitrogen migration and single-cell-protein production in high-ammonia piggery wastewater - Qian Lu; Huankai Li; Hui Liu; Zhimin Xu; Pascal E. Saikaly; Wenxiang Zhang (Environmental Research, 2024)

Evidence of autotrophic direct electron transfer denitrification (DETD) by Thiobacillus species enriched on biocathodes during deep polishing of effluent from a municipal wastewater treatment plant - Haoyong Li; Yuhao Xu; He Dong; Jie Min; Haiyu Xu; Dezhi Sun; Xinying Liu; Yan Dang; Bin Qiu; Thomas Mennella; Dawn E Holmes (Chemical Engineering Journal, 2024)

Appraisal of Urban Waterlogging and Extent Damage Situation after the Devastating Flood - Shan-e-hyder Soomro; Muhammad Waseem Boota; Xiaotao Shi; Gul-e-Zehra Soomro; Yinghai Li; Muhammad Tayyab; Caihong Hu; Chengshuai Liu; Yuanyang Wang; Junaid Abdul Wahid; Mairaj Hyder Alias Aamir Soomro; Jiali Guo; et al. (Water Resources Management, 2024)

Fault control on sedimentation in the southern gentle slope of the Dongying Sag, Bohai Bay Basin - Hong Chen; Shaohua Xu; Chang'e Cai; Wenliang Shang; Jinxin Mao; Zhengjian Xu; Xiaogang Li; Jianping Liu; Nanxin Yin; Kaitong Luo; Chao Lei; Runchao Wang; et al. (Marine and Petroleum Geology, 2024)

Isomer-specific cardiotoxicity induced by tricresyl phosphate in zebrafish embryos/larvae - Xun’e Yi; Haiyu Qin; Guangyu Li; Ren Kong; Chunsheng Liu (Journal of Hazardous Materials, 2024)

Self-assembly of cascade nanoenzyme glucose oxidase encapsulated in copper benzenedicarboxylate for wearable sweat-glucose colorimetric sensors with smartphone readout - Binghua Fan; Yongjun Wu; Hongchao Guo; Fei Yu; Li-e Liu; Songcheng Yu; Jia Wang; Yilin Wang (Analytica Chimica Acta, 2024)

Machine learning framework develops neutrophil extracellular traps model for clinical outcome and immunotherapy response in lung adenocarcinoma - A. Xuan Han; B. Yaping Long; C. Yao Li; D. Di Huang; E. Qi Xiong; F. Jinfeng Li; G. Liangliang Wu; Qiaowei Liu; G. Bo Yang; H. Yi Hu (Apoptosis, 2024)

Phylogenetic origin of an insect fauna at the boundary of the Palaearctic and Oriental realms: Evidence from ‘site‐based’ mitogenomics - Rui‐E Nie; Lu‐Lu Li; Anderson Feijó; Mei‐Xia Yang; Ming Bai; Thomas J. Creedy; Xu Jin; Jia‐Sheng Hao; Yong‐Ying Ruan; Hua‐Xi Liu; Beulah H. Garner; Ladislav Bocak; et al. (Journal of Biogeography, 2024)
Aim Knowledge of taxonomy and species distributions in highly diverse lineages of invertebrates remains too incomplete for the study of biogeographical patterns at the global scale. This limits the understanding of processes leading to the formation and maintenance of boundaries between major biogeographical realms. Site‐based metagenomic approaches may provide an alternative source of data for inference of historical processes of in situ speciation and interchange among biogeographical regions. We applied the methodology to explore the historical biogeography of the Qinling Mountains at the boundary of the Oriental and Palaearctic regions. Location The focal area in the Qinling Mountains; sites in Borneo, Panama, and Spain, representing the Oriental, Neotropical and Palaearctic faunas. Time Period Contemporary. Major Taxa Studied Chrysomelidae, a group of ~40,000 species with worldwide distribution. Methods Mass‐trapped insects were subjected to deep Illumina DNA sequencing and mitochondrial genome assembly, followed by phylogenetic analysis and historical biogeographical inference on a dated tree. The methodology produced 622 mitogenomes (304 newly sequenced) each representing a morphologically distinct species. Results Ancestral area reconstruction revealed that the Qinling fauna is a composite of distinct clades that, respectively, have Oriental or Palaearctic ancient origins, while in situ speciation and local clade formation were limited. The global diversity of Chrysomelidae consists of regionalised deep clades at the level of the major zoogeographic realms, which remain recognisable where these realms abut in the Qinling mountains. Yet, the Qinling fauna is clearly distinct from the source areas although local lineage ages are generally Main Conclusions The Qinling fauna is a composite of clades that have either Oriental or Palaearctic origin, indicating the important role of immigration at the realm boundary. Global site‐based phylogenetic analyses based on metagenomic sequencing can address previously intractable questions about the historical biogeography of poorly studied groups even without a fully developed taxonomy.

Activation of Notch Signaling Pathway is involved in Extracellular Matrix Degradation in human induced pluripotent stem cells chondrocytes induced by HT-2 toxin - Peilin Meng; Huan Liu; Li Liu; Yan Wen; Feng'e Zhang; Yanan Zhang; Yumeng Jia; Yingang Zhang; Feng Zhang; Xiong Guo (Food and Chemical Toxicology, 2024)

Research on runoff process vectorization and integration of deep learning algorithms for flood forecasting - Chengshuai Liu; Wenzhong Li; Caihong Hu; Tianning Xie; Yunqiu Jiang; Runxi Li; Shan-e-hyder Soomro; Yuanhao Xu (Journal of Environmental Management, 2024)

Interpretable baseflow segmentation and prediction based on numerical experiments and deep learning - Qiying Yu; Chen Shi; Yungang Bai; Jianghui Zhang; Zhenlin Lu; Yingying Xu; Wenzhong Li; Chengshuai Liu; Shan-e-hyder Soomro; Lu Tian; Caihong Hu (Journal of Environmental Management, 2024)

Effect of Ba2+ on the biomineralization of Ca2+ and Mg2+ ions induced by Bacillus licheniformis - Huaxiao Yan; Xiaofei Zhu; Zhenjiang Li; Zhiyong Liu; Shengping Jin; Xiaotong Zhou; Zuozhen Han; Jusun Woo; Long Meng; Xiangqun Chi; Chao Han; Yanyang Zhao; et al. (World Journal of Microbiology and Biotechnology, 2024)

New Record Ocean Temperatures and Related Climate Indicators in 2023 - Lijing Cheng; John Abraham; Kevin E. Trenberth; Tim Boyer; Michael E. Mann; Jiang Zhu; Fan Wang; Fujiang Yu; Ricardo Locarnini; John Fasullo; Fei Zheng; Yuanlong Li; et al. (Advances in Atmospheric Sciences, 2024)
The global physical and biogeochemical environment has been substantially altered in response to increased atmospheric greenhouse gases from human activities. In 2023, the sea surface temperature (SST) and upper 2000 m ocean heat content (OHC) reached record highs. The 0–2000 m OHC in 2023 exceeded that of 2022 by 15 ± 10 ZJ (1 Zetta Joules = 10 21 Joules) (updated IAP/CAS data); 9 ± 5 ZJ (NCEI/NOAA data). The Tropical Atlantic Ocean, the Mediterranean Sea, and southern oceans recorded their highest OHC observed since the 1950s. Associated with the onset of a strong El Niño, the global SST reached its record high in 2023 with an annual mean of ∼0.23°C higher than 2022 and an astounding > 0.3°C above 2022 values for the second half of 2023. The density stratification and spatial temperature inhomogeneity indexes reached their highest values in 2023.

How effective is twitter (X) social media data for urban flood management? - Shan-e-hyder Soomro; Muhammad Waseem Boota; Haider M. Zwain; Gul-e-Zehra Soomro; Xiaotao Shi; Jiali Guo; Yinghai Li; Muhammad Tayyab; Mairaj Hyder Alias Aamir Soomro; Caihong Hu; Chengshuai Liu; Yuanyang Wang; et al. (Journal of Hydrology, 2024)

Whole transcriptome mapping reveals the lncRNA regulatory network of TFP5 treatment in diabetic nephropathy - Hongyan Luo; Lirong Yang; Guoqing Zhang; Xi Bao; Danna Ma; Bo Li; Li Cao; Shilu Cao; Shunyao Liu; Li Bao; Jing E; Yali Zheng (Genes & Genomics, 2024)

Biological characteristics of Cordyceps militaris single mating-type strains - Xiu’E Li; Xin Wang; Fengji Liang; Zhaoxin Wang; Wenshuo Liu; Yupeng Ge; Shude Yang; Yu Liu; Yin Li; Xianhao Cheng; Weihuan Li (Archives of Microbiology, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Changes in soil microbe-mediated carbon, nitrogen and phosphorus cycling during spontaneous succession in abandoned Pb Zn mining areas - Sichen Wang; Xinqi Yuan; Ting Li; Jie Yang; Luoqi Zhao; Duanyang Yuan; Zhaolai Guo; Chang'e Liu; Changqun Duan (Science of The Total Environment, 2024)

Advances in wastewater analysis revealing the co-circulating viral trends of noroviruses and Omicron subvariants - Teresa Kumblathan; Yanming Liu; Mary Crisol; Xiaoli Pang; Steve E. Hrudey; X. Chris Le; Xing-Fang Li (Science of The Total Environment, 2024)

Recycling of waste polyethylene in asphalt and its performance enhancement methods: A critical literature review - Hui Li; Yuzhao Han; E Guangxun; Yang Sun; Lei Wang; Xufei Liu; Jiaxing Ren; Zhijie Lin (Journal of Cleaner Production, 2024)

Aligning nature-based solutions with ecosystem services in the urban century - Roy P. Remme; Megan Meacham; Kara E. Pellowe; Erik Andersson; Anne D. Guerry; Benjamin Janke; Lingling Liu; Eric Lonsdorf; Meng Li; Yuanyuan Mao; Christopher Nootenboom; Tong Wu; et al. (Ecosystem Services, 2024)

Oral delivery of berberine by liver-targeted zwitterionic nanoparticles to overcome multi-intestinal barriers and extend insulin treatment duration - Yuhong Ma; Caihua Li; Fuwei Han; Yunzhu Liu; Umm E Hani; Yinan Zhong; Dechun Huang; Wei Chen; Hongliang Qian (Chemical Engineering Journal, 2024)

Peacock flaunting tail inspired-multiple interactions between black phosphorene and glass powder with safety shield fire of epoxy resin - Kunxin Wang; Guoming Yuan; Zhijun Liu; Hui Yang; Yang Li; Xiu-e Li; Kun Wu; Jun Shi (Chemical Engineering Journal, 2024)

Global multifaceted biodiversity patterns, centers, and conservation needs in angiosperms - Ao Luo; Yaoqi Li; Nawal Shrestha; Xiaoting Xu; Xiangyan Su; Yichao Li; Tong Lyu; Kilara Waris; Zhiyao Tang; Xiaojuan Liu; Luxiang Lin; Yongsheng Chen; et al. (Science China Life Sciences, 2024)

Quantitative prediction and spatial analysis of structural fractures in deep shale gas reservoirs within complex structural zones: A case study of the Longmaxi Formation in the Luzhou area, southern Sichuan Basin, China - Cunhui Fan; Shan Nie; Hu Li; Ahmed E. Radwan; Qingchuan Pan; Xiangchao Shi; Jing Li; Yongyang Liu; Yi Guo (Journal of Asian Earth Sciences, 2024)

Soybean-processing wastewater as an electron donor for denitrification - Yue Ma; Chong Tan; Songyun Chen; Haiyun Zhang; Fei Liu; Xu Peng; Mo Li; Yongming Zhang; Bruce E. Rittmann (International Biodeterioration & Biodegradation, 2024)

Effects of Nitrogen and Phosphorus Limitation on the Growth and Phosphorus Allocation of Alfalfa (Medicago sativa L.) - Yafei Hu; Cheng Qian; Xin Zhao; Junlin Li; Lin Wang; Dalin Liu; Xin’e Li (Journal of Soil Science and Plant Nutrition, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

Soil microbial communities' contributions to soil ecosystem multifunctionality in the natural restoration of abandoned metal mines - Ting Li; Sichen Wang; Chang'e Liu; Yadong Yu; Mingming Zong; Changqun Duan (Journal of Environmental Management, 2024)

Transient heat transfer simulation, sensitivity analysis, and design optimization of shallow ground heat exchangers with hollow-finned structures for enhanced performance of ground-coupled heat pumps - Basher Hassan Al-Kbodi; Taha Rajeh; Mohamed E. Zayed; Yang Li; Jun Zhao; Jiahui Wu; Yuanyuan Liu (Energy and Buildings, 2024)

Quaternary ammonium salt coated air filter for bioaerosol removal from building indoor air - Huixin Jiang; Kai Li; David E. Graham; Attelia Hollander; Mariappan P. Paranthaman; M. Muneeshwaran; Xiaoli Liu; Merlin Theodore; Tolga Aytug; Keju An; Kashif Nawaz (Building and Environment, 2024)

Simple, fast and eco-friendly micro-solid phase extraction based on thiol and ionic liquid bi-functional nanofibers membrane for the determination of sulfonamides in environmental water - Ningge Jian; Yuanyuan Dai; Hongli Liu; Niu Wu; Li-e Liu; Di Wu; Yongjun Wu (Analytica Chimica Acta, 2024)

Effects of konjac glucan-nan/low-acyl gellan edible coatings loaded thymol-β-cyclodextrin microcapsules on postharvest blueberry - Jie Ding; Chunyan Liu; Peng Huang; Hongying Li; Yan Liu; Dur E. Sameen; Yuwei Zhang; Yaowen Liu; Wen Qin (Food Chemistry, 2024)

Bacterial, short-chain fatty acid and gas profiles of partially hydrolyzed guar gum in vitro fermentation by human fecal microbiota - Xiong-E Pi; Hao Fu; Xiao-Xia Yang; Zai-Chun Yu; Wei-Lin Teng; Yinjun Zhang; Xue-Wei Ye; Hui Hui Quan; Li-Zhi Lu; Wei Liu (Food Chemistry, 2024)

Stress ratio sensitivity—a novel parameter for evaluating the shearing-based structural characteristic of loess - Meng Yao; Hui-e Chen; Hui Li; Qing wang; Yan Han; Qingbo Yu; Yibo Liu (Bulletin of Engineering Geology and the Environment, 2024)

Co-metabolic biodegradation of chlorinated ethene in an oxygen- and ethane-based membrane biofilm reactor - Zifang Chi; Xinyang Liu; Huai Li; Shen Liang; Yi-Hao Luo; Chen Zhou; Bruce E. Rittmann (Science of The Total Environment, 2023)

Moderate altitude exposure impacts host fasting blood glucose and serum metabolome by regulation of the intestinal flora - Dan Liu; Xiaoyan Gao; Xiaoran Huang; Yanqun Fan; Yu-E Wang; Yuelin Zhang; Xuanfu Chen; Jielu Wen; Haiwei He; Yimei Hong; Ying Liang; Yuxiao Zhang; et al. (Science of The Total Environment, 2023)

Hirsutinolide-type sesquiterpenoids with anti-prostate cancer activity from Cyanthillium cinereum - Song Ang; Chun Liu; Peng Hong; Lei Yang; Gui'e Hu; Xi Zheng; Jingwei Jin; Rihui Wu; Wing-Leung Wong; Kun Zhang; Lishe Gan; Dongli Li (Phytochemistry, 2023)

Polyguluronic acid alleviates doxorubicin-induced cardiotoxicity by suppressing Peli1-NLRP3 inflammasome-mediated pyroptosis - E Zhang; Chuangeng Shang; Mingtao Ma; Xuanfeng Zhang; Yu Liu; Shuliang Song; Xia Li (Carbohydrate Polymers, 2023)

Metabolome and Transcriptome Association Analysis Reveals the Link Between Pigmentation and Nutrition Utilization in the Juveniles of Sea Cucumber Holothuria leucospilota - Jiasheng Huang; Zixuan E; Wenjie Pan; Zhi Li; Tiehao Lin; Chunhua Ren; Peng Luo; Bo Ma; Yang Liu; Xugan Wu; Chaoqun Hu; Xiao Jiang; et al. (Marine Biotechnology, 2023)

The microbial mechanisms by which long-term heavy metal contamination affects soil organic carbon levels - Zhineng Xiao; Changqun Duan; Shiyu Li; Ji Chen; Changhui Peng; Rongxiao Che; Chang'e Liu; Yin Huang; Runran Mei; Liangliang Xu; Pengfei Luo; Yadong Yu (Chemosphere, 2023)

Dust diffusion laws during partition excavation by boom-type roadheader in a metro tunnel - Ning Liu; Xiong Wu; E Deng; Yi-Qing Ni; Wei-Chao Yang; Guo-Zhi Li (Tunnelling and Underground Space Technology, 2023)

Direct identification of total and missing OH reactivities from light-duty gasoline vehicle exhaust in China based on LP-LIF measurement - Xuehui Liu; Zibing Yuan; Qing'e Sha; Shengrong Lou; Hongli Wang; Xin Li; Junyu Zheng; Bin Yuan; Min Shao (Journal of Environmental Sciences, 2023)

The effect of long-term controlled-release urea application on the relative abundances of plant growth-promoting microorganisms - Feng Gao; Zeli Li; Yongxiang Gao; E. Gaoyang; Mingyang Li; Chuanfu Li; Yunlong Cheng; Tianjiao Zhang; Shuo Wang; Liang Wu; Zhanbo Wei; Wenkui Zheng; et al. (European Journal of Agronomy, 2023)

TFP5, a Peptide Derived from Cdk5 Activator p35, Protects Pancreatic β Cells from Glucose Toxicity - S.-Y. Liu; S.-L. Cao; H.-Y. Luo; L. Bao; J. E; B. Li; X.-M. Lan; G.-Q. Zhang; X. Bao; Y.-L. Zheng (Bulletin of Experimental Biology and Medicine, 2023)

Konjac glucomannan/low-acyl gellan gum edible coating containing thymol microcapsule regulates cell wall polysaccharides disassembly and delays postharvest softening of blueberries - Peng Huang; Jie Ding; Chunyan Liu; Hongying Li; Chenlin Wang; Yezi Lin; Dur E. Sameen; Md Alomgir Hossen; Mingrui Chen; Jing Yan; Yaowen Liu; Wen Qin (Postharvest Biology and Technology, 2023)

Research on the distribution of S species in the pressure oxidation leaching process of SrS solution - Siming Chen; Dongping Duan; Yanjiang Li; Yan Liu; E Zhou (Minerals Engineering, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Composition, function and succession of bacterial communities in the tomato rhizosphere during continuous cropping - Lv Su; Huatai Li; Jing Wang; Wenting Gao; Xia Shu; Xiting Sun; Kesu Wang; Yan Duan; Yunpeng Liu; Eiko E. Kuramae; Ruifu Zhang; Biao Shen (Biology and Fertility of Soils, 2023)

A New Machine-Learning Extracting Approach to Construct a Knowledge Base: A Case Study on Global Stromatolites over Geological Time - Xiaobo Zhang; Hao Li; Qiang Liu; Zhenhua Li; Claire E. Reymond; Min Zhang; Yuangeng Huang; Hongfei Chen; Zhong-Qiang Chen (Journal of Earth Science, 2023)

Co-generation of hydroxyl and sulfate radicals via homogeneous and heterogeneous bi-catalysis with the EO-PS-EF tri-coupling system for efficient removal of refractory organic pollutants - Wanlin Yang; Zejun Deng; Libin Liu; Kechao Zhou; Sharel P. E; Lingcong Meng; Li Ma; Qiuping Wei (Water Research, 2023)

Non-uniform dissolved oxygen distribution and high sludge concentration enhance simultaneous nitrification and denitrification in a novel air-lifting reactor for municipal wastewater treatment: A pilot-scale study - Yun Li; Shujie Liu; Lanlan Lu; Jinghou Wang; Guangrong Huang; Fuming Chen; Jian-e Zuo (Bioresource Technology, 2023)

Delays in heading and improvements in both spikelet number and spike length are associated with the Aegilops tausschii photoperiod-sensitive ppd-D1b allele - Shunzong Ning; Laibin Zhao; Shijie Li; Shengke Li; Tianqing Zang; Yu’e Liu; Hongkun Yang; Xuejiao Chen; Xue Chen; Yingjin Yi; Ming Hao; Lianquan Zhang; et al. (Cereal Research Communications, 2023)

Identification of general features in soil fungal communities modulated by phenolic acids - Lv Su; Huatai Li; Xiting Sun; Kesu Wang; Xia Shu; Wenting Gao; Yunpeng Liu; Eiko E. Kuramae; Biao Shen; Ruifu Zhang (Applied Soil Ecology, 2023)

Global mapping of urban thermal anisotropy reveals substantial potential biases for remotely sensed urban climates - Huilin Du; Wenfeng Zhan; Zihan Liu; E. Scott Krayenhoff; TC Chakraborty; Lei Zhao; Lu Jiang; Pan Dong; Long Li; Fan Huang; Shasha Wang; Yuyue Xu (Science Bulletin, 2023)

Paleoclimatic and anthropogenic impacts on the environment of Southwest China since 33 ka based on multiproxy analysis of karst depression deposits - Xing Tian; Xiaoyong Long; Shu’e Luo; Min Cao; Ji Li; Yuchuan Sun; Sibo Zeng; Ze Wu; Chuan Liu; Lidan Lei; Thomas J. Algeo; Yongjun Jiang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

An efficient method to enhance recovery and detection of SARS-CoV-2 RNA in wastewater - Teresa Kumblathan; Yanming Liu; Yuanyuan Qiu; Lilly Pang; Steve E. Hrudey; X. Chris Le; Xing-Fang Li (Journal of Environmental Sciences, 2023)

Enhanced Degradation of Acid Orange 52 Using a Polyextremophilic Ascomycete in Stirred Tank Bioreactor - Qandeel Laraib; Maryam Shafique; Muhammad Ali Versiani; Khitab Gul; Uroosa Ejaz; Haji Muhammad; Sehar Afshan Naz; Drauzio E. N. Rangel; Alene Alder-Rangel; Kousar Yasmeen; Nusrat Jabeen; Jing Liu; et al. (Water, Air, & Soil Pollution, 2023)

Migraine, chronic kidney disease and kidney function: observational and genetic analyses - Wenqiang Zhang; Li Zhang; Luo Yang; Chenghan Xiao; Xueyao Wu; Peijing Yan; Huijie Cui; Chao Yang; Jingwei Zhu; Xuan Wu; Mingshuang Tang; Yutong Wang; et al. (Human Genetics, 2023)
Epidemiological studies demonstrate an association between migraine and chronic kidney disease (CKD), while the genetic basis underlying the phenotypic association has not been investigated. We aimed to help avoid unnecessary interventions in individuals with migraine through the investigation of phenotypic and genetic relationships underlying migraine, CKD, and kidney function. We first evaluated phenotypic associations using observational data from UK Biobank ( N = 255,896). We then investigated genetic relationships leveraging genomic data in European ancestry for migraine ( N case / N control = 48,975/540,381), CKD ( N case / N control = 41,395/439,303), and two traits of kidney function (estimated glomerular filtration rate [eGFR, N = 567,460] and urinary albumin-to-creatinine ratio [UACR, N = 547,361]). Observational analyses suggested no significant association of migraine with the risk of CKD (HR = 1.13, 95% CI = 0.85–1.50). While we did not find any global genetic correlation in general, we identified four specific genomic regions showing significant for migraine with eGFR. Cross-trait meta-analysis identified one candidate causal variant (rs1047891) underlying migraine, CKD, and kidney function. Transcriptome-wide association study detected 28 shared expression–trait associations between migraine and kidney function. Mendelian randomization analysis suggested no causal effect of migraine on CKD (OR = 1.03, 95% CI = 0.98–1.09; P = 0.28). Despite a putative causal effect of migraine on an increased level of UACR (log-scale-beta = 0.02, 95% CI = 0.01–0.04; P = 1.92 × 10 −3 ), it attenuated to null when accounting for both correlated and uncorrelated pleiotropy. Our work does not find evidence supporting a causal association between migraine and CKD. However, our study highlights significant biological pleiotropy between migraine and kidney function. The value of a migraine prophylactic treatment for reducing future CKD in people with migraine is likely limited.

Metal mixture exposure and the risk for immunoglobulin A nephropathy: Evidence from weighted quantile sum regression - Shaohui Liu; Li’e Zhang; Na Luo; Mingjun Wang; Chuanqiao Tang; Jiajun Jing; Hao Chen; Qiuhua Hu; Lina Tan; Xiaoli Ma; Yunfeng Zou (Environmental Science and Pollution Research, 2023)

Sinomenine ameliorates rheumatoid arthritis by modulating tryptophan metabolism and activating aryl hydrocarbon receptor via gut microbiota regulation - Zheng-Meng Jiang; Su-Ling Zeng; Tian-Qing Huang; Yang Lin; Fang-Fang Wang; Xing-Jiao Gao; Jing Li; Ping Li; E-Hu Liu (Science Bulletin, 2023)

Astrochronology and sedimentary noise modeling of Pliensbachian (Early Jurassic) sea-level changes, Paris Basin, France - Rui Zhang; David B. Kemp; Nicolas Thibault; Mads E. Jelby; Mingsong Li; Chunju Huang; Yu Sui; Zhixiang Wang; Dongyang Liu; Shizhen Jia (Earth and Planetary Science Letters, 2023)

Western diet unmasks transient low-level vinyl chloride-induced tumorigenesis; potential role of the (epi-)transcriptome - Silvia Liu; Liqing He; Olivia B. Bannister; Jiang Li; Regina D. Schnegelberger; Charis-Marie Vanderpuye; Andrew D. Althouse; Francisco J. Schopfer; Banrida Wahlang; Matthew C. Cave; Satdarshan P. Monga; Xiang Zhang; et al. (Toxicology and Applied Pharmacology, 2023)

Inter-regional environmental inequality under lasting pandemic exacerbated by residential response - Chunjin Li; Jintai Lin; Lulu Chen; Qi Cui; Yu Liu; Erin E. McDuffie; Mingxi Du; Hao Kong; Jingxu Wang (Science of The Total Environment, 2023)

A rapid chemometrics model for antioxidant substance mining of Chinese dwarf cherry [Cerasus humilis (Bge.) Sok.] based on polyphenol profile and antioxidant capacity of 30 germplasms - Yushi Zhang; Qingyu Cui; Chang-e Guo; Xiaobing Zhang; Shupeng Liu; Xiaoxue Wang; Jinjiang Zhao; Zihan Zhao; Weidong Li (Food Bioscience, 2023)

Long-term application of controlled-release potassium chloride increases maize yield by affecting soil bacterial ecology, enzymatic activity and nutrient supply - Zeli Li; Lixue Qiu; Tianjiao Zhang; Gaoyang E; Lili Zhang; Lingli Wang; Liang Wu; Yanfeng Wang; Yunfeng Zhang; Jun Dong; Wenjing Li; Zhiguang Liu; et al. (Field Crops Research, 2023)

Another Year of Record Heat for the Oceans - Lijing Cheng; John Abraham; Kevin E. Trenberth; John Fasullo; Tim Boyer; Michael E. Mann; Jiang Zhu; Fan Wang; Ricardo Locarnini; Yuanlong Li; Bin Zhang; Fujiang Yu; et al. (Advances in Atmospheric Sciences, 2023)
Changes in ocean heat content (OHC), salinity, and stratification provide critical indicators for changes in Earth’s energy and water cycles. These cycles have been profoundly altered due to the emission of greenhouse gasses and other anthropogenic substances by human activities, driving pervasive changes in Earth’s climate system. In 2022, the world’s oceans, as given by OHC, were again the hottest in the historical record and exceeded the previous 2021 record maximum. According to IAP/CAS data, the 0–2000 m OHC in 2022 exceeded that of 2021 by 10.9 ± 8.3 ZJ (1 Zetta Joules = 10 21 Joules); and according to NCEI/NOAA data, by 9.1 ± 8.7 ZJ. Among seven regions, four basins (the North Pacific, North Atlantic, the Mediterranean Sea, and southern oceans) recorded their highest OHC since the 1950s. The salinity-contrast index, a quantification of the “salty gets saltier—fresh gets fresher” pattern, also reached its highest level on record in 2022, implying continued amplification of the global hydrological cycle. Regional OHC and salinity changes in 2022 were dominated by a strong La Niña event. Global upper-ocean stratification continued its increasing trend and was among the top seven in 2022.

Decreasing expression of Prohibitin-2 lowers the oncogenicity of renal cell carcinoma cells by suppressing eIF4E-mediated oncogene translation via MNK inhibition - Jie Yang; Gang Li; Yue'e Huang; Ying Liu (Toxicology and Applied Pharmacology, 2023)

Machine learning and deep learning based on the small FT-MIR dataset for fine-grained sampling site recognition of boletus tomentipes - Jian-E Dong; Jieqing Li; Honggao Liu; Yuan-Zhong Wang (Food Research International, 2023)

Recent advances in the fabrication of pH-sensitive indicators films and their application for food quality evaluation - Qingying Luo; Alomgir Hossen; Dur E Sameen; Saeed Ahmed; Jianwu Dai; Suqing Li; Wen Qin; Yaowen Liu (Critical Reviews in Food Science and Nutrition, 2023)

Simple and efficient solid phase extraction based on molecularly imprinted resorcinol–formaldehyde resin nanofibers for determination of trace sulfonamides in animal-origin foods - Yuanyuan Dai; Niu Wu; Li-e Liu; Fei Yu; Yongjun Wu; Ningge Jian (Food Chemistry, 2023)

Trends in elemental Pb concentrations within atmospheric PM2.5 and associated risk to human health in major cities of China - Qian Cui; Liangzhong Li; Yaqiang Cao; Bo Yang; Lindou Liu; Xiaoyan Dong; Yu'e Cha; Hongjie Ruan; Song Tang; Qiong Wang (Environmental Pollution, 2023)

A 1000-year hydroclimate record from the Asian summer monsoon-Westerlies transition zone in the northeastern Qinghai-Tibetan Plateau - Luo Qin; Guangxin Liu; Xiangzhong Li; E. Chongyi; Jiang Li; Changrun Wu; Xin Guan; Yuan Wang (Climatic Change, 2023)

Spatio‐temporal patterns in the woodiness of flowering plants - Ao Luo; Xiaoting Xu; Yunpeng Liu; Yaoqi Li; Xiangyan Su; Yichao Li; Tong Lyu; Dimitar Dimitrov; Markku Larjavaara; Shijia Peng; Yongsheng Chen; Qinggang Wang; et al. (Global Ecology and Biogeography, 2023)
Aim Woody and herbaceous habits represent one of the most distinct contrasts among angiosperms, and the proportion of woody species in floras (i.e., “woodiness” hereafter) represents a fundamental structural element of plant diversity. Despite its core influence on ecosystem processes, spatio‐temporal patterns in woodiness remain poorly understood. Here, we aim to demonstrate the global spatio‐temporal patterns in angiosperm woodiness and their relationship with environmental factors. Location Global. Time period Cenozoic, 66 Ma to present. Major taxa studied Angiosperms. Methods Using newly compiled data on the growth forms and distributions of c . 300,000 angiosperm species and an angiosperm phylogeny, we mapped the current global geographical patterns in angiosperm woodiness, reconstructed ancestral states of growth forms through the angiosperm phylogeny and demonstrated the Cenozoic evolutionary dynamics of woodiness. We evaluated the relationships between woodiness and current climate and palaeoclimate. Results We found that c . 42.7% of angiosperms are woody. Woodiness decreased spatially from the equator towards high latitudes, temporally since the early Cenozoic. Temperature was the best predictor of the spatio‐temporal decline in woodiness and was positively correlated with woodiness. Despite the temporal decline in woodiness, macroevolutionary herbaceous‐to‐woody transitions increased through time and contributed to the evolution of woody floras in temperate drylands, whereas the opposite transitions decreased through time and contributed to herbaceous floras in tropical and subtropical drylands. Main conclusions Our study improves understanding of the spatio‐temporal dynamics of angiosperm woodiness. Our findings suggest that temperature is likely to be a determinant of spatio‐temporal variations in woodiness, highlighting the role of temperature in maintaining the growth form composition of ecosystems. Our study also calls for attention to growth form transitions (e.g., secondary woodiness) in temperate drylands that have been neglected before.

How Comamonas testosteroni and Rhodococcus ruber enhance nitrification in the presence of quinoline - Ge Zhu; Haiyun Zhang; Ru Yuan; Meng Huang; Fei Liu; Mo Li; Yongming Zhang; Bruce E. Rittmann (Water Research, 2023)

Multi-stage planning of LID-GREI urban drainage systems in response to land-use changes - Yu Zhang; Mo Wang; Dongqing Zhang; Zhongming Lu; Amin E. Bakhshipour; Ming Liu; Zhiyu Jiang; Jianjun Li; Soon Keat Tan (Science of The Total Environment, 2023)

Calcification of cell membranes: From ions to minerals - Xiao Gao; Jie Li; Kaiming Hu; Yanyang Zhao; Yu Han; Fang Liu; Maurice E. Tucker; Zuozhen Han (Chemical Geology, 2023)

Oxidative stress induced by plasma-activated water stimulates astaxanthin production in Phaffia rhodozyma - Wenshao Li; Carlos H. Luna-Flores; Raveendra Anangi; Renwu Zhou; Xinle Tan; Marius Jessen; Lian Liu; Rusen Zhou; Tianqi Zhang; Alexander Gissibl; Patrick J. Cullen; Kostya (Ken) Ostrikov; et al. (Bioresource Technology, 2023)

RecruitNet : A global database of plant recruitment networks - Miguel Verdú; Jose L. Garrido; Julio M. Alcántara; Alicia Montesinos‐Navarro; Salomón Aguilar; Marcelo A. Aizen; Ali A. Al‐Namazi; Mohamed Alifriqui; David Allen; Kristina J. Anderson‐Teixeira; Cristina Armas; Jesús M. Bastida; et al. (Ecology, 2023)
Plant recruitment interactions (i.e., what recruits under what) shape the composition, diversity, and structure of plant communities. Despite the huge body of knowledge on the mechanisms underlying recruitment interactions among species, we still know little about the structure of the recruitment networks emerging in ecological communities. Modeling and analyzing the community‐level structure of plant recruitment interactions as a complex network can provide relevant information on ecological and evolutionary processes acting both at the species and ecosystem levels. We report a data set containing 143 plant recruitment networks in 23 countries across five continents, including temperate and tropical ecosystems. Each network identifies the species under which another species recruits. All networks report the number of recruits (i.e., individuals) per species. The data set includes >850,000 recruiting individuals involved in 118,411 paired interactions among 3318 vascular plant species across the globe. The cover of canopy species and open ground is also provided. Three sampling protocols were used: (1) The Recruitment Network (RN) protocol (106 networks) focuses on interactions among established plants (“canopy species”) and plants in their early stages of recruitment (“recruit species”). A series of plots was delimited within a locality, and all the individuals recruiting and their canopy species were identified; (2) The paired Canopy‐Open (pCO) protocol (26 networks) consists in locating a potential canopy plant and identifying recruiting individuals under the canopy and in a nearby open space of the same area; (3) The Georeferenced plot (GP) protocol (11 networks) consists in using information from georeferenced individual plants in large plots to infer canopy‐recruit interactions. Some networks incorporate data for both herbs and woody species, whereas others focus exclusively on woody species. The location of each study site, geographical coordinates, country, locality, responsible author, sampling dates, sampling method, and life habits of both canopy and recruit species are provided. This database will allow researchers to test ecological, biogeographical, and evolutionary hypotheses related to plant recruitment interactions. There are no copyright restrictions on the data set; please cite this data paper when using these data in publications.

Implicit satiety goals and food-related expectations predict portion size in older adults: Findings from the BAMMBE cohort - Aimee E. Pink; Li Ling Lee; Dorrain Yanwen Low; Yifan Yang; LaiGuan Zoey Fong; Alicia Yi Hui Kang; Peijia Liu; Hyejin Kim; Yulan Wang; Parasuraman Padmanabhan; Lynne Cobiac; Balázs Gulyás; et al. (Appetite, 2023)

In situ formed CaSO4 on waste dander biochar to inhibit the mineralization of soil organic carbon - Cheng Ji; Shuyi Yang; Ying Cheng; Lin Liu; Daohan Wang; Shujing Zhu; Tao E; Yun Li (Science of The Total Environment, 2023)

Toughing epoxy nanocomposites with graphene-encapsulated liquid metal framework - Da Li; E Peng; Fei Lu; Baolong Wang; Yibo Shen; Pengxiang Liu; Li Liu; Yudong Huang; Zhen Hu (Chemical Engineering Journal, 2023)

Effect of posaconazole on the concentration of intravenous and oral cyclosporine in patients undergoing hematopoietic stem cell transplantation - Li-E Zhu; Hui-Ping Huang; Yi-Peng Cai; Yan Wang; Bao-Hua Xu; Mao-Bai Liu; Xue-Mei Wu (European Journal of Clinical Pharmacology, 2022)

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Assessing the joint effects of brain aging and gut microbiota on the risks of psychiatric disorders - Huijie Zhang; Li Liu; Shiqiang Cheng; Yumeng Jia; Yan Wen; Xuena Yang; Peilin Meng; Chun’e Li; Chuyu Pan; Yujing Chen; Zhen Zhang; Jingxi Zhang; et al. (Brain Imaging and Behavior, 2022)

Electrospun nanofibers food packaging: trends and applications in food systems - Dur E. Sameen; Saeed Ahmed; Rui Lu; Rui Li; Jianwu Dai; Wen Qin; Qing Zhang; Suqing Li; Yaowen Liu (Critical Reviews in Food Science and Nutrition, 2022)

Evidence of interactions between sharks and Indo‐Pacific humpback dolphins ( Sousa chinensis ) in the northern South China Sea - Agathe Serres; Wenzhi Lin; Eric E. G. Clua; Mingli Lin; Mingming Liu; Songhai Li (Marine Mammal Science, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

An adaptive data cleaning framework: a case study of the water quality monitoring system in China - Zeng Chen; Peng Jiang; Jun Liu; Song Zheng; Zhenyu Shan; Zhihua Li; Huan Xu; Igor V. Bychkov; Alexei E. Hmelnov (Hydrological Sciences Journal, 2022)

River Flood Susceptibility and Basin Maturity Analyzed Using a Coupled Approach of Geo-morphometric Parameters and SWAT Model - Shan-e-hyder Soomro; Caihong Hu; Muhammad Waseem Boota; Zubair Ahmed; Liu Chengshuai; Han Zhenyue; Li Xiang; Mairaj Hyder Alias Aamir Soomro (Water Resources Management, 2022)

Immunostimulatory effect of quaternary degree and acetyl group of quaternized chitosan on macrophages RAW 264.7 - Xiaomin Li; Rong’e Xing; Chaojie Xu; Song Liu; Yukun Qin; Kecheng Li; Huahua Yu; Pengcheng Li (Journal of Oceanology and Limnology, 2022)

Impact of land use on surface water quality: a case study of active agriculturally disturbed basin in China - L. Zhang; X. Liu; H. Wei; C. Yang; E. Li; Z. Wang (International Journal of Environmental Science and Technology, 2022)

Research progress on antimicrobial materials for food packaging - Saeed Ahmed; Dur E. Sameen; Rui Lu; Rui Li; Jianwu Dai; Wen Qin; Yaowen Liu (Critical Reviews in Food Science and Nutrition, 2022)

Sterols and triterpenoids from Ganoderma lucidum and their reversal activities of tumor multidrug resistance - Min Wu; Cui-e Shen; Qiao-fa Lin; Jin-yi Zhong; Yan-fei Zhou; Ben-chen Liu; Jian-hua Xu; Zhi-qiang Zhang; Peng Li (Natural Product Research, 2022)

Another Record: Ocean Warming Continues through 2021 despite La Niña Conditions - Lijing Cheng; John Abraham; Kevin E. Trenberth; John Fasullo; Tim Boyer; Michael E. Mann; Jiang Zhu; Fan Wang; Ricardo Locarnini; Yuanlong Li; Bin Zhang; Zhetao Tan; et al. (Advances in Atmospheric Sciences, 2022)
The increased concentration of greenhouse gases in the atmosphere from human activities traps heat within the climate system and increases ocean heat content (OHC). Here, we provide the first analysis of recent OHC changes through 2021 from two international groups. The world ocean, in 2021, was the hottest ever recorded by humans, and the 2021 annual OHC value is even higher than last year’s record value by 14 ± 11 ZJ (1 zetta J = 10 21 J) using the IAP/CAS dataset and by 16 ± 10 ZJ using NCEI/NOAA dataset. The long-term ocean warming is larger in the Atlantic and Southern Oceans than in other regions and is mainly attributed, via climate model simulations, to an increase in anthropogenic greenhouse gas concentrations. The year-to-year variation of OHC is primarily tied to the El Niño-Southern Oscillation (ENSO). In the seven maritime domains of the Indian, Tropical Atlantic, North Atlantic, Northwest Pacific, North Pacific, Southern oceans, and the Mediterranean Sea, robust warming is observed but with distinct inter-annual to decadal variability. Four out of seven domains showed record-high heat content in 2021. The anomalous global and regional ocean warming established in this study should be incorporated into climate risk assessments, adaptation, and mitigation.

Circular RNA screening identifies circMYLK4 as a regulator of fast/slow myofibers in porcine skeletal muscles - Haigang Cao; Jieming Liu; Tianning Du; Yihao Liu; Xiaoyu Zhang; Yuan Guo; Jie Wang; Xiaomin Zhou; Xiao Li; Gongshe Yang; Xin’e Shi (Molecular Genetics and Genomics, 2022)
The type of myofiber is related to the quality of meat. The slow oxidized myofiber helps to increase the tenderness and juiciness of muscle. Numerous studies have shown that circRNA plays a key role in skeletal muscle development. However, the role of circRNA in porcine skeletal myofiber types is unclear. In this study, we performed high-throughput RNA sequencing to study the differential expression of circRNA in the longissimus dorsi and the soleus muscle. A total of 40,757 circRNAs were identified, of which 181 were significantly different. Interestingly, some circRNAs were involved in metabolism pathways, AMPK, FoxO, and PI3K-Akt signaling pathways. Besides, we focused on a novel circRNA-circMYLK4. By injecting circMYLK4-AAV into piglets, we found that circMYLK4 significantly increased the mRNA and protein levels of the slow muscle marker genes. In summary, our study laid an essential foundation for further research of circRNA in myofiber type conversion and higher meat quality.

Integer ambiguity resolution and precise positioning for tight integration of BDS-3, GPS, GALILEO, and QZSS overlapping frequencies signals - Guang’e Chen; Bofeng Li; Zhiteng Zhang; Tianxia Liu (GPS Solutions, 2022)

Chlorogenic acid inhibits apoptosis in thiram-induced tibial dyschondroplasia via intrinsic pathway - Jialu Zhang; Bihao Luo; Juanjuan Liu; Muhammad Waqas; Muhammad Fakhar-e-Alam Kulyar; Kangkang Guo; Jiakui Li (Environmental Science and Pollution Research, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

A 168-year temperature recording based on tree rings and latitude differences in temperature changes in northeast China - Yangao Jiang; Yuting Cao; Junhui Zhang; Zhuo Li; Guoqiang Shi; Shijie Han; Cassius E. O. Coombs; Chuan Liu; Xiaoguang Wang; Junwei Wang; Lin Hao; Qi Xu; et al. (International Journal of Biometeorology, 2021)

Emergy-based ecological efficiency evaluation and optimization method for logistics park - Cui Wang; Cuixia Zhang; Fagang Hu; Yuan Wang; Li’e Yu; Conghu Liu (Environmental Science and Pollution Research, 2021)

Bacterial Viruses Subcommittee and Archaeal Viruses Subcommittee of the ICTV: update of taxonomy changes in 2021 - Mart Krupovic; Dann Turner; Vera Morozova; Mike Dyall-Smith; Hanna M. Oksanen; Rob Edwards; Bas E. Dutilh; Susan M. Lehman; Alejandro Reyes; Diana P. Baquero; Matthew B. Sullivan; Jumpei Uchiyama; et al. (Archives of Virology, 2021)
In this article, we – the Bacterial Viruses Subcommittee and the Archaeal Viruses Subcommittee of the International Committee on Taxonomy of Viruses (ICTV) – summarise the results of our activities for the period March 2020 – March 2021. We report the division of the former Bacterial and Archaeal Viruses Subcommittee in two separate Subcommittees, welcome new members, a new Subcommittee Chair and Vice Chair, and give an overview of the new taxa that were proposed in 2020, approved by the Executive Committee and ratified by vote in 2021. In particular, a new realm, three orders, 15 families, 31 subfamilies, 734 genera and 1845 species were newly created or redefined (moved/promoted).

Spartina alterniflora saltmarsh soil organic carbon properties and sources in coastal wetlands - Jin-e Liu; Dailan Deng; Caiyu Zou; Ruiming Han; Yue Xin; Zihao Shu; Li-min Zhang (Journal of Soils and Sediments, 2021)

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Isolation and identification of antimicrobial metabolites from sea anemone-derived fungus Emericella sp. SMA01 - Yang Yue; Huahua Yu; Rongfeng Li; Linfeng Hu; Song Liu; Rong’e Xing; Pengcheng Li (Journal of Oceanology and Limnology, 2021)

Soil engineering by ants facilitates plant compensation for large herbivore removal of aboveground biomass - Zhiwei Zhong; Xiaofei Li; Dirk Sanders; Yiming Liu; Ling Wang; Yvette K. Ortega; Dean E. Pearson; Deli Wang (Ecology, 2021)
The interplay between top‐down and bottom‐up processes determines ecosystem productivity. Yet, the factors that mediate the balance between these opposing forces remain poorly understood. Furthering this challenge, complex and often cryptic factors like ecosystem engineering and trait‐mediated interactions may play major roles in mediating the outcomes of top‐down and bottom‐up interactions. In semiarid grasslands of northeastern China, we conducted a large‐scale, three‐year experiment to evaluate how soil engineering by ants and plasticity in plants independently and jointly influenced the top‐down effects of grazing by a ubiquitous herbivore (cattle) on aboveground standing biomass of the dominant perennial grass, Leymus chinensis . Herbivory had strong top‐down effects, reducing L. chinensis AB by 25% relative to baseline levels without cattle or ants. In contrast, soil engineering by ants facilitated weak bottom‐up effects in the absence of herbivory. However, in the presence of herbivory, soil engineering effects were strong enough to fully offset herbivore removal of aboveground biomass. This outcome was mediated by L. chinensis ’s plasticity in reallocating growth from below‐ to aboveground biomass, a result linked to additive effects of engineers and herbivores increasing soil N availability and engineering effects improving soil structure. Soil engineering increased soil N by 12%, promoting aboveground biomass. Herbivores increased soil N by 13% via defecation, but this increase failed to offset their reductions in aboveground biomass in isolation. However, when combined, engineers and herbivores increased soil N by 26% and engineers improved soil bulk density, facilitating L. chinensis to shift resource allocations from below‐ to aboveground biomass sufficiently to fully offset herbivore suppression of aboveground biomass. Our results demonstrate that soil engineering and trait‐mediated effects of plant plasticity can strongly mediate the outcome of top‐down and bottom‐up interactions. These cryptic but perhaps ubiquitous processes may help to explain the long‐debated phenomenon of plant compensatory responses to large grazers.

Initial ingestion of CMV-infected plants reduces subsequent aphid performance - Xiao-bin Shi; Jun Deng; Zhuo Zhang; Shuo Yan; Li-min Zheng; Shu-e Sun; Yang Gao; Xu-guo Zhou; De-yong Zhang; Yong Liu (Arthropod-Plant Interactions, 2021)

Responses of submerged macrophytes and periphyton to warming under two nitrogen scenarios: A microcosm study - Yang Liu; Celina Aznarez; Erik Jeppesen; Hu He; Wei Li; Eti E. Levi; Juan Pablo Pacheco; Yu Cao (Hydrobiologia, 2021)

Regional Comparison of Snow Leopard (Panthera uncia) Diet using DNA Metabarcoding - Charlotte E. Hacker; Matthew Jevit; Shafqat Hussain; Ghulam Muhammad; Bariushaa Munkhtsog; Bayaraa Munkhtsog; Yuguang Zhang; Diqiang Li; Yanlin Liu; John D. Farrington; Farida Balbakova; Azat Alamanov; et al. (Biodiversity and Conservation, 2021)

Whole-cell bioreporters for evaluating petroleum hydrocarbon contamination - Bo Jiang; Yizhi Song; Zengjun Liu; Wei E. Huang; Guanghe Li; Songqiang Deng; Yi Xing; Dayi Zhang (Critical Reviews in Environmental Science and Technology, 2021)

High increase in biodegradability of coking wastewater enhanced by Mn ore tailings in Fenton/O3 combined processes - H. Liu; T. Xu; C. Li; W. Liu; E. Lichtfouse (International Journal of Environmental Science and Technology, 2021)

Knowledge of Cervical Cancer, Human Papilloma Virus (HPV) and HPV Vaccination Among Women in Northeast China - Yu-e Ning; Yao Liu; Xiao-yu Xu; Xin-yu Zhang; Ning Wang; Li-qiang Zheng (Journal of Cancer Education, 2020)
This study aimed to research the understanding and knowledge of cervical cancer, human papilloma virus (HPV), and HPV vaccination, and the acceptance of HPV vaccination, among a population of women in northeastern China. A cross-sectional survey was carried out by questionnaire to investigate knowledge of cervical cancer, HPV, and HPV vaccination. The 230 female participants were native residents of northeastern China, and their ages ranged between 18 and 65 years. Questionnaires were randomly acquired by the respondents from online and paper questionnaire distribution. The questionnaire included questions on three major aspects to record people’s perceptions of cervical cancer, HPV, and vaccines. Of the sample of 230 women surveyed, 80.9% had heard of cervical cancer, but understanding was only 15.7%; 38.3% knew about HPV; 20% knew about HPV vaccine; 39.6% agreed to receive HPV vaccination, and the remainder were mainly concerned about its safety and effectiveness. Data analysis showed that age, family income, and whether there was experience of screening all influenced knowledge of cervical cancer, but this was not statistically significant. The level of education had no obvious effect on the degree of knowledge about cervical cancer; however, with an improvement in education, women’s awareness of HPV vaccine improved significantly ( p < 0.05). Women who have received cervical cancer screening had significantly greater knowledge about cervical cancer and HPV than those with no screening ( p < 0.05). Women in northeastern China have little knowledge of cervical cancer, HPV, and HPV vaccine, lack disease knowledge, and hold a skeptical attitude about HPV vaccination. Medical institutions are the main channel providing information to these women.

SNP of AHSA2 gene in three cattle breeds using snapshot technology - Shu-Zhu Cheng; E. Guang-Xin; Cheng-Li Liu; Wang-Dui Basang; Yan-Bin Zhu; Ri-Su Na; Yan-Guo Han; Yan Zeng; Xiao Wang; Wei-Wei Ni; Bai-Gao Yang; Xing-Hai Duan; et al. (Journal of Genetics, 2020)

PSD-93 Interacts with SynGAP and Promotes SynGAP Ubiquitination and Ischemic Brain Injury in Mice - Qingxiu Zhang; Hui Yang; Hong Gao; Xiaomei Liu; Qingjie Li; Rong Rong; Zhenqian Liu; Xiu-e Wei; Liping Kong; Yun Xu; Liangqun Rong (Translational Stroke Research, 2020)

Seasonal Rainfall Forecasts for the Yangtze River Basin of China in Summer 2019 from an Improved Climate Service - Philip E. Bett; Nicola Martin; Adam A. Scaife; Nick Dunstone; Gill M. Martin; Nicola Golding; Joanne Camp; Peiqun Zhang; Chris D. Hewitt; Leon Hermanson; Chaofan Li; Hong-Li Ren; et al. (Journal of Meteorological Research, 2020)

Noise does not equal bias in assessing the evolutionary history of the angiosperm flora of China: A response to Qian (2019) - Li‐Min Lu; Hai‐Hua Hu; Dan‐Xiao Peng; Bing Liu; Jian‐Fei Ye; Tuo Yang; Hong‐Lei Li; Miao Sun; Stephen A. Smith; Pamela S. Soltis; Douglas E. Soltis; Zhi‐Duan Chen (Journal of Biogeography, 2020)
In response to our paper on the evolutionary history of the Chinese flora, Qian suggests that certain features of the divergence time estimation employed might have led to biased conclusions in Lu et al (2018). Here, we consider Qian's specific criticisms, explore the extent of uncertainty in the data and demonstrate that (i) no systematic bias toward dates that are too young or too old is detected in Lu et al.; (ii) constraint of the crown age of angiosperms does not bias the generic ages estimated by Lu et al.; and (iii) ages derived from the Chinese regional phylogeny do not bias the conclusions reported by Lu et al. All these analyses confirm that the conclusions reported previously are robust. We argue that, like many large‐scale biodiversity analyses, sources of noise in divergence time estimation are to be expected, but these should not be confused with bias.

Molecular characterization of gut microbial shift in SD rats after death for 30 days - Huan Li; E. Yang; Siruo Zhang; Jing Zhang; Lu Yuan; Ruina Liu; Shakir Ullah; Qi Wang; Nosheen Mushtaq; Yi Shi; Cuihong An; Zhenyuan Wang; et al. (Archives of Microbiology, 2020)

Effect of Chinese Rice Wine on the Endogenous Protease Activity, Myofibrillar Degradation, and Quality Characteristics in Topmouth Culter ( Culter alburnus ) - Fan Wang; Jia-Liang He; Tursunay Turgun; Da-E Ge; Nurgul Rahman; Jian-Zhong Zhou; Xiao-Li Liu (Journal of Aquatic Food Product Technology, 2020)

Preparation, characterization, and antifungal evaluation of a new type of aminourea chitooligosaccharide derivatives - Jun Zhu; Song Liu; Yukun Qin; Rong’e Xing; Huahua Yu; Xiaolin Chen; Pengcheng Li (Journal of Oceanology and Limnology, 2020)

PI3K/Akt pathway is involved in the activation of RAW 264.7 cells induced by hydroxypropyltrimethyl ammonium chloride chitosan - Yue Yang; Rong’e Xing; Song Liu; Yukun Qin; Kecheng Li; Huahua Yu; Pengcheng Li (Journal of Oceanology and Limnology, 2020)

Mitogenomic phylogeny of the Naticidae (Gastropoda: Littorinimorpha) reveals monophyly of the Polinicinae - Hongyue Liu; Yi Yang; Shao'e Sun; Lingfeng Kong; Qi Li (Zoologica Scripta, 2020)
The Naticidae is a species‐rich family of predatory marine gastropods with substantial interspecific morphological diversity. The classification of the Naticidae has been traditionally based on morphology data, but the phylogenetic relationships within the family are debated due to conflicting molecular results, especially regarding the monophyly of subfamilies Polinicinae and Naticinae. To further resolve the phylogenetic controversies within the Naticidae, we undertake a phylogenetic approach using 14 newly sequenced complete or nearly complete (only lacking a control region) mitochondrial genomes. Both the maximum likelihood and Bayesian inference analyses supported monophyly of the Polinicinae, but paraphyly of the Naticinae due to the placement of the enigmatic genus Notocochlis . The ancestral character reconstruction suggests that the operculum, a character that currently defines the two subfamilies, evolved from an ancestor with a calcareous operculum in the evolutionary history of naticids. In addition, the chronogram estimates that naticids was originated in late Triassic (about 227 million years ago), consistent with previous hypotheses. Our study highlights the importance of using complete mitochondrial genomes while reconstructing phylogenetic relationships within the Naticidae. The evolution scenario of the naticid operculum contributes new insights into the classification of Naticidae.

Study of the closure temperature of (U-Th)/He in detrital zircon obtained from natural evolution samples - Chang’e Cai; Nansheng Qiu; Huili Li; Daniel F. Stockli; Jian Chang; Nian Liu (Science China Earth Sciences, 2020)

Arsenic Distribution, Accumulation and Tolerance Mechanisms of Typha angustifolia in Different Phenological Growth Stages - Guiying Yang; Huan Zhong; Xue Liu; Chang’e Liu; Shiyu Li; Lei Hou; Yungen Liu; Yan Wang; Wei Ren; Changqun Duan (Bulletin of Environmental Contamination and Toxicology, 2020)

Atmospheric mercury accumulation rate in northeastern China during the past 800 years as recorded by the sediments of Tianchi Crater Lake - Tao Zhan; Xin Zhou; Wenhan Cheng; Xiaoqing He; Luyao Tu; Xiaoyan Liu; Junyi Ge; Yuanyun Xie; Jun Zhang; Yongfa Ma; E Li; Yansong Qiao (Environmental Science and Pollution Research, 2020)

Methane production in the oxygenated water column of a perennially ice‐covered Antarctic lake - Wei Li; John E. Dore; August J. Steigmeyer; Yong‐Joon Cho; Ok‐Sun Kim; Yongqin Liu; Rachael M. Morgan‐Kiss; Mark L. Skidmore; John C. Priscu (Limnology and Oceanography, 2020)
Aerobic methane production in aquatic ecosystems impacts the global atmospheric budget of methane, but the extent, mechanism, and taxa responsible for producing this greenhouse gas are not fully understood. Lake Bonney (LB), a perennially ice‐covered Antarctic lake, has cold hypersaline waters underlying an oxygenated freshwater layer. We present temporal methane concentration profiles in LB indicating methane production in the oxygenated (> 200% air saturation) water. Experiments amended with methylphosphonate (MPn) yielded methane generation, suggesting in situ methanogenesis via the carbon‐phosphorus (C‐P) lyase pathway. Enrichment cultures from the lake were used to isolate five bacterial strains capable of generating methane when supplied with MPn as the sole P source. Based on 16S rRNA gene sequencing, the isolates belong to the Proteobacteria (closely related to Marinomonas , Hoeflea , and Marinobacter genera) and Bacteroidetes ( Algoriphagus genus). 16S rRNA metagenomic sequencing confirms the presence of these taxa in LB. None of the isolated species were reported to be capable to produce methane. In addition, orthologs of the phosphoenolpyruvate mutase gene ( PepM ) and methylphosphonate synthase ( MPnS ), enzymes involved in phosphonate and MPn biosynthesis, were widely spread in the LB shotgun metagenomic libraries; genes related to C‐P lyase pathways ( phn gene clusters) were also abundant. 16S rRNA and mcrA genes of anaerobic methanogens were absent in both 16S rRNA and metagenomics libraries. These data reveal that in situ aerobic biological methane production is likely a significant source of methane in LB.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

One bis-indole alkaloid-voacamine from Voacanga africana Stapf: biological activity evaluation of PTP1B in vitro utilizing enzymology method based on SPRi expriment - Yan-Qiu Wang; Hong-Xiang Li; Xiao-Chun Liu; Jin-Shuang Zhao; Rong-Qiang Liu; Wen-ying Huai; Wei-Jun Ding; Tian-E Zhang; Yun Deng (Natural Product Research, 2019)

Distinctiveness, speciation and demographic history of the rare endemic conifer Juniperus erectopatens in the eastern Qinghai-Tibet Plateau - Jingjing Xu; Xinya Song; Markus Ruhsam; Tingxuan Liu; Jialiang Li; Linda E. Neaves; Jibin Miao; Siyu Xie; Qingyu Meng; Kangshan Mao (Conservation Genetics, 2019)

The effect of substrate grain size on burrowing ability and distribution characteristics of Perinereis aibuhitensis - Tao Sun; Chun’e Liu; Xingzuo Li; Dongzhengyang An; Hairui Yu; Zheng Ma; Feng Liu (Acta Oceanologica Sinica, 2019)

Supporting Spartina : Interdisciplinary perspective shows Spartina as a distinct solid genus - Alejandro Bortolus; Paul Adam; Janine B. Adams; Malika L. Ainouche; Debra Ayres; Mark D. Bertness; Tjeerd J. Bouma; John F. Bruno; Isabel Caçador; James T. Carlton; Jesus M. Castillo; Cesar S. B. Costa; et al. (Ecology, 2019)
In 2014, a DNA‐based phylogenetic study confirming the paraphyly of the grass subtribe Sporobolinae proposed the creation of a large monophyletic genus Sporobolus , including (among others) species previously included in the genera Spartina , Calamovilfa , and Sporobolus. Spartina species have contributed substantially (and continue contributing) to our knowledge in multiple disciplines, including ecology, evolutionary biology, molecular biology, biogeography, experimental ecology, biological invasions, environmental management, restoration ecology, history, economics, and sociology. There is no rationale so compelling to subsume the name Spartina as a subgenus that could rival the striking, global iconic history and use of the name Spartina for over 200 yr. We do not agree with the subjective arguments underlying the proposal to change Spartina to Sporobolus . We understand the importance of both the objective phylogenetic insights and of the subjective formalized nomenclature and hope that by opening this debate we will encourage positive feedback that will strengthen taxonomic decisions with an interdisciplinary perspective. We consider that the strongly distinct, monophyletic clade Spartina should simply and efficiently be treated as the genus Spartina .

Intravitreal Ets1 siRNA alleviates choroidal neovascularization in a mouse model of age-related macular degeneration - Manhui Zhu; Li Jiang; You Yuan; Lili Chen; Xiaojuan Liu; Juan Liang; Qiujian Zhu; Dongmei Ding; E. Song (Cell and Tissue Research, 2019)

Copy number variation of bovine SHH gene is associated with body conformation traits in Chinese beef cattle - Mei Liu; Bo Li; Tao Shi; Yongzhen Huang; George E. Liu; Xianyong Lan; Chuzhao Lei; Hong Chen (Journal of Applied Genetics, 2019)

Computational detection and experimental validation of segmental duplications and associated copy number variations in water buffalo ( Bubalus bubalis ) - Shuli Liu; Xiaolong Kang; Claudia R. Catacchio; Mei Liu; Lingzhao Fang; Steven G. Schroeder; Wenli Li; Benjamin D. Rosen; Daniela Iamartino; Leopoldo Iannuzzi; Tad S. Sonstegard; Curtis P. Van Tassell; et al. (Functional & Integrative Genomics, 2019)

Changes in retinal and choroidal morphology after cerebrospinal fluid pressure reduction: a Beijing iCOP study - Lu Liu; Xiaoxia Li; Hanspeter E. Killer; Kai Cao; Jing Li; Ningli Wang (Science China Life Sciences, 2019)

Leveraging linkage evidence to identify low-frequency and rare variants on 16p13 associated with blood pressure using TOPMed whole genome sequencing data - Karen Y. He; Xiaoyin Li; Tanika N. Kelly; Jingjing Liang; Brian E. Cade; Themistocles L. Assimes; Lewis C. Becker; Amber L. Beitelshees; Adam P. Bress; Yen-Pei Christy Chang; Yii-Der Ida Chen; Paul S. de Vries; et al. (Human Genetics, 2019)

Adsorption performance and mechanisms of Pb(II), Cd(II), and Mn(II) removal by a β-cyclodextrin derivative - Mengjiao Zhang; Liyun Zhu; Changhua He; Xiaojun Xu; Zhengyang Duan; Shuli Liu; Mingyao Song; Shumin Song; Jiemei Shi; Yu’e Li; Guangzhu Cao (Environmental Science and Pollution Research, 2019)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Focusing quorum sensing signalling by nano‐magnetic assembly - Yongguang Guan; Chen‐Yu Tsao; David N. Quan; Ying Li; Lei Mei; Yingying Song; Boce Zhang; Yi Liu; Gregory F. Payne; William E. Bentley; Qin Wang (Environmental Microbiology, 2018)
Summary Quorum sensing (QS) exists widely among bacteria, enabling a transition to multicellular behaviour after bacterial populations reach a particular density. The coordination of multicellularity enables biotechnological application, dissolution of biofilms, coordination of virulence, and so forth. Here, a method to elicit and subsequently disperse multicellular behaviour among QS‐negative cells is developed using magnetic nanoparticle assembly. We fabricated magnetic nanoparticles (MNPs, ∼5 nm) that electrostatically collect wild‐type (WT) Escherichia coli BL21 cells and brings them into proximity of bioengineered E. coli [CT104 (W3110 lsrFG − luxS − pCT6 + pET‐DsRed)] reporter cells that exhibit a QS response after receiving autoinducer‐2 (AI‐2). By shortening the distance between WT and reporter cells (e.g., increasing local available AI‐2 concentrations), the QS response signalling was amplified four‐fold compared to that in native conditions without assembly. This study suggests potential applications in facilitating intercellular communication and modulating multicellular behaviours based on user‐specified designs.

Evolution of interspecies unilateral incompatibility in the relatives of Arabidopsis thaliana - Ling Li; Bo Liu; Xiaomei Deng; Hainan Zhao; Hongyan Li; Shilai Xing; Della D. Fetzer; Mengya Li; Mikhail E. Nasrallah; June B. Nasrallah; Pei Liu (Molecular Ecology, 2018)
The evolutionary concurrence of intraspecies self‐incompatibility ( SI ) and explosive angiosperm radiation in the Cretaceous have led to the hypothesis that SI was one of the predominant drivers of rapid speciation in angiosperms. Interspecies unilateral incompatibility ( UI ) usually occurs when pollen from a self‐compatible ( SC ) species is rejected by the pistils of a SI species, while the reciprocal pollination is compatible ( UC ). Although this SI × SC type UI is most prevalent and viewed as a prezygotic isolation barrier to promote incipient speciation of angiosperms, comparative evidence to support such a role is lacking. We show that SI × SI type UI in SI species pairs is also common in the well‐characterized accessions representing the four major lineages of the Arabidopsis genus and is developmentally regulated. This allowed us to reveal a strong correlation between UI strength and species divergence in these representative accessions. In addition, analyses of a SC accession and the pseudo‐self‐compatible ( psc ) spontaneous mutant of Arabidopsis lyrata indicate that UI shares, at least, common pollen rejection pathway with SI . Furthermore, genetic and genomic analyses of SI × SI type UI in A. lyrata × A. arenosa species pair showed that two major‐effect quantitative trait loci are the stigma and pollen‐side determinant of UI , respectively, which could be involved in heterospecies pollen discrimination. By revealing a close link between UI and SI pathway, particularly between UI and species divergence in these representative accessions, our findings establish a connection between SI and speciation. Thus, the pre‐existence of SI system would have facilitated the evolution of UI and accordingly promote speciation.

Overexpression of VpPR10.1 by an efficient transformation method enhances downy mildew resistance in V. vinifera - Hang Su; Yun-Tong Jiao; Fang-Fang Wang; Yue-E Liu; Wei-Li Niu; Guo-Tian Liu; Yan Xu (Plant Cell Reports, 2018)

In vitro prebiotic effects of seaweed polysaccharides - Xiaolin Chen; Yuhao Sun; Linfeng Hu; Song Liu; Huahua Yu; Rong’e Xing; Rongfeng Li; Xueqin Wang; Pengcheng Li (Journal of Oceanology and Limnology, 2018)

Long-term (≥20 years) application of fertilizers and straw return enhances soil carbon storage: a meta-analysis - Yu’e Li; Shengwei Shi; Muhammad Ahmed Waqas; Xiaoxia Zhou; Jianling Li; Yunfan Wan; Xiaobo Qin; Qingzhu Gao; Shuo Liu; Andreas Wilkes (Mitigation and Adaptation Strategies for Global Change, 2018)

Transient receptor potential vanilloid-3 (TRPV3) activation plays a central role in cardiac fibrosis induced by pressure overload in rats via TGF-β1 pathway - Yan Liu; Hanping Qi; Mingyao E; Pilong Shi; Qianhui Zhang; Shuzhi Li; Ye Wang; Yonggang Cao; Yunping Chen; Lina Ba; Jingquan Gao; Wei Huang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

Reduced deep regional cerebral venous oxygen saturation in hemodialysis patients using quantitative susceptibility mapping - Chao Chai; Saifeng Liu; Linlin Fan; Lei Liu; Jinping Li; Chao Zuo; Tianyi Qian; E. Mark Haacke; Wen Shen; Shuang Xia (Metabolic Brain Disease, 2018)

A new compound, methylbergenin along with eight known compounds with cytotoxicity and anti-inflammatory activity from Ardisia japonica - Ke-Yun Yu; Wei Wu; Shang-Zhen Li; Li-Li Dou; Le-Le Liu; Ping Li; E-Hu Liu (Natural Product Research, 2017)

SLCO1B1 521T > C polymorphism associated with rosuvastatin-induced myotoxicity in Chinese coronary artery disease patients: a nested case–control study - Ju-E Liu; Xiao-Ying Liu; Sheng Chen; Yan Zhang; Li-Yun Cai; Min Yang; Wei-Hua Lai; Bin Ren; Shi-Long Zhong (European Journal of Clinical Pharmacology, 2017)

Pancreas specific expression of oncogenes in a porcine model - Martin F. Berthelsen; Morten M. Callesen; Tanja S. Østergaard; Ying Liu; Rong Li; Henrik Callesen; Frederik Dagnæs-Hansen; Stephen Hamilton-Dutoit; Jannik E. Jakobsen; Martin K. Thomsen (Transgenic Research, 2017)

Trans-ethnic fine-mapping of genetic loci for body mass index in the diverse ancestral populations of the Population Architecture using Genomics and Epidemiology (PAGE) Study reveals evidence for multiple signals at established loci - Lindsay Fernández-Rhodes; Jian Gong; Jeffrey Haessler; Nora Franceschini; Mariaelisa Graff; Katherine K. Nishimura; Yujie Wang; Heather M. Highland; Sachiko Yoneyama; William S. Bush; Robert Goodloe; Marylyn D. Ritchie; et al. (Human Genetics, 2017)

Aquatic species dominate organic matter in Qinghai Lake during the Holocene: Evidence from eolian deposits around the lake - Fangming Zeng; Xiangjun Liu; Xiangzhong Li; Chongyi E (Journal of Earth Science, 2017)

In Situ Enzymatic Conversion of Nannochloropsis oceanica IMET1 Biomass into Fatty Acid Methyl Esters - Yao Wang; Yi-Ying Lee; Tonya M. Santaus; Charles E. Newcomb; Jin Liu; Chris D. Geddes; Chengwu Zhang; Qiang Hu; Yantao Li (BioEnergy Research, 2017)

Functional genes and thermophilic microorganisms responsible for arsenite oxidation from the shallow sediment of an untraversed hot spring outlet - Ye Yang; Yao Mu; Xian-Chun Zeng; Weiwei Wu; Jie Yuan; Yichen Liu; E. Guoji; Feng Luo; Xiaoming Chen; Hao Li; Jianing Wang (Ecotoxicology, 2017)

Impacts of potassium ferrate(VI) on the growth and organic matter accumulation, production, and structural changes in the cyanobacterium Microcystis aeruginosa - Shu-yu Liu; Jingling Xu; Wen-li Chen; Berthold E. David; Minghong Wu; Fang Ma (Environmental Science and Pollution Research, 2017)

Evaluation and Optimization of Chemical Treatments for Reducing Yellow Discoloration of Channel Catfish ( Ictalurus punctatus ) Fillets During Cold Storage - Yilin Li; Yifen Wang; Claude E. Boyd; Terrill R. Hanson; Shaoyang Liu (Journal of Aquatic Food Product Technology, 2017)

Composite modification mechanism of cationic modifier to amphoteric modified kaolin and its effects on surface characteristics - W. B. Li; Z. Liu; Z. F. Meng; S. Ren; S. E. Xu; Y. Zhang; M. Y. Wang (International Journal of Environmental Science and Technology, 2016)

Basin-Scale Study on the Multiphase Distribution, Source Apportionment and Risk Assessment of PAHs in the Hai River Water System - Rufeng Li; Xian’e Zhang; Yanzhen Liu; Su Yin; Jingling Liu; Chenghong Feng (Archives of Environmental Contamination and Toxicology, 2016)

Microsatellite records for volume 8, issue 2 - Dareen Almojil; Maria Cristina Arias; Rochelle R. Beasley; Yiyong Chen; Rulon W. Clark; Yinghui Dong; Zhiguo Dong; Natalie Forsdick; Elaine Françoso; E. González-Ortegón; A. M. González-Tizón; Linsheng Gui; et al. (Conservation Genetics Resources, 2016)

The role of exogenous electron donors for accelerating 2,4,6-trichlorophenol biotransformation and mineralization - Ning Yan; Rongjie Li; Hua Xu; Ling Li; Lihui Yang; Yongming Zhang; Rui Liu; Bruce E. Rittmann (Biodegradation, 2016)

Over-expression of a WRKY transcription factor gene BoWRKY6 enhances resistance to downy mildew in transgenic broccoli plants - Ming Jiang; Qing-e Liu; Zhen-Ning Liu; Jin-Zhi Li; Cai-Ming He (Australasian Plant Pathology, 2016)

UV photolysis for enhanced phenol biodegradation in the presence of 2,4,6-trichlorophenol (TCP) - Jiaxiu Song; Wenbing Wang; Rongjie Li; Jun Zhu; Yongming Zhang; Rui Liu; Bruce E. Rittmann (Biodegradation, 2016)

Fine mapping of qhir8 affecting in vivo haploid induction in maize - Chenxu Liu; Wei Li; Yu Zhong; Xin Dong; Haixiao Hu; Xiaolong Tian; Lele Wang; Baojian Chen; Chen Chen; Albrecht E. Melchinger; Shaojiang Chen (Theoretical and Applied Genetics, 2015)

Changes in the abundance and structure of bacterial communities under long-term fertilization treatments in a peanut monocropping system - Wuxing Liu; Qingling Wang; Baozhan Wang; Xiaobing Wang; Ashley E. Franks; Ying Teng; Zhengao Li; Yongming Luo (Plant and Soil, 2015)

Clinical characteristics of 154 patients suspected of having Ebola virus disease in the Ebola holding center of Jui Government Hospital in Sierra Leone during the 2014 Ebola outbreak - T. Yan; J. Mu; E. Qin; Y. Wang; L. Liu; D. Wu; H. Jia; Z. Li; T. Guo; X. Wang; Y. Qin; Y. Li; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Extreme variation of sulfur isotopic compositions in pyrite from the Qiuling sediment-hosted gold deposit, West Qinling orogen, central China: an in situ SIMS study with implications for the source of sulfur - Lei Chen; Xian-hua Li; Jian-wei Li; Albert H. Hofstra; Yu Liu; Alan E. Koenig (Mineralium Deposita, 2015)

Near infrared radiation protects against oxygen-glucose deprivation-induced neurotoxicity by down-regulating neuronal nitric oxide synthase (nNOS) activity in vitro - Zhanyang Yu; Zhaoyu Li; Ning Liu; Yunneng Jizhang; Thomas J. McCarthy; Clark E. Tedford; Eng H. Lo; Xiaoying Wang (Metabolic Brain Disease, 2015)

Erratum to: Use of a whole-cell bioreporter, Acinetobacter baylyi, to estimate the genotoxicity and bioavailability of chromium(VI)-contaminated soils - Bo Jiang; Di Zhu; Yizhi Song; Dayi Zhang; Zengjun Liu; Xu Zhang; Wei E. Huang; Guanghe Li (Biotechnology Letters, 2015)

Heterologous biosynthesis of costunolide in Escherichia coli and yield improvement - Hua Yin; Yi-bin Zhuang; E-e Li; Hui-ping Bi; Wei Zhou; Tao Liu (Biotechnology Letters, 2015)

Near infrared radiation rescues mitochondrial dysfunction in cortical neurons after oxygen-glucose deprivation - Zhanyang Yu; Ning Liu; Jianhua Zhao; Yadan Li; Thomas J. McCarthy; Clark E. Tedford; Eng H. Lo; Xiaoying Wang (Metabolic Brain Disease, 2015)

Mechanistic Aspects of the Photodynamic Inactivation of Vancomycin-Resistant Enterococci Mediated by 5-Aminolevulinic Acid and 5-Aminolevulinic Acid Methyl Ester - Chengcheng Liu; Yingli Zhou; Li Wang; Lei Han; Jin’e Lei; Hafiz Muhammad Ishaq; Jiru Xu (Current Microbiology, 2015)

How inhibiting nitrification affects nitrogen cycle and reduces environmental impacts of anthropogenic nitrogen input - Chunlian Qiao; Lingli Liu; Shuijin Hu; Jana E. Compton; Tara L. Greaver; Quanlin Li (Global Change Biology, 2015)
Anthropogenic activities, and in particular the use of synthetic nitrogen (N) fertilizer, have doubled global annual reactive N inputs in the past 50–100 years, causing deleterious effects on the environment through increased N leaching and nitrous oxide (N 2 O) and ammonia ( NH 3 ) emissions. Leaching and gaseous losses of N are greatly controlled by the net rate of microbial nitrification. Extensive experiments have been conducted to develop ways to inhibit this process through use of nitrification inhibitors ( NI ) in combination with fertilizers. Yet, no study has comprehensively assessed how inhibiting nitrification affects both hydrologic and gaseous losses of N and plant nitrogen use efficiency. We synthesized the results of 62 NI field studies and evaluated how NI application altered N cycle and ecosystem services in N‐enriched systems. Our results showed that inhibiting nitrification by NI application increased NH 3 emission (mean: 20%, 95% confidential interval: 33–67%), but reduced dissolved inorganic N leaching (−48%, −56% to −38%), N 2 O emission (−44%, −48% to −39%) and NO emission (−24%, −38% to −8%). This amounted to a net reduction of 16.5% in the total N release to the environment. Inhibiting nitrification also increased plant N recovery (58%, 34–93%) and productivity of grain (9%, 6–13%), straw (15%, 12–18%), vegetable (5%, 0–10%) and pasture hay (14%, 8–20%). The cost and benefit analysis showed that the economic benefit of reducing N's environmental impacts offsets the cost of NI application. Applying NI along with N fertilizer could bring additional revenues of $163 ha −1 yr −1 for a maize farm, equivalent to 8.95% increase in revenues. Our findings showed that NI s could create a win‐win scenario that reduces the negative impact of N leaching and greenhouse gas production, while increases the agricultural output. However, NI 's potential negative impacts, such as increase in NH 3 emission and the risk of NI contamination, should be fully considered before large‐scale application.

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

Use of a whole-cell bioreporter, Acinetobacter baylyi, to estimate the genotoxicity and bioavailability of chromium(VI)-contaminated soils - Bo Jiang; Di Zhu; Yizhi Song; Dayi Zhang; Zengjun Liu; Xu Zhang; Wei E. Huang; Guanghe Li (Biotechnology Letters, 2015)

ICE1 demethylation drives the range expansion of a plant invader through cold tolerance divergence - H. J. Xie; H. Li; D. Liu; W. M. Dai; J. Y. He; S. Lin; H. Duan; L. L. Liu; S. G. Chen; X. L. Song; B. E. Valverde; S. Qiang (Molecular Ecology, 2015)
Cold tolerance adaption is a crucial determinant for the establishment and expansion of invasive alien plants into new cold environments; however, its evolutionary mechanism is poorly understood. Crofton weed ( Ageratina adenophora ), a highly invasive alien plant, is continuously spreading across subtropical areas in China, north‐eastward from the first colonized south‐western tropical regions, through cold tolerance evolution. Close relations between the cold tolerance levels of 34 populations, represented by 147 accessions, and the latitude, extreme lowest temperature, coldest month average temperature, and invasion period have provided direct insight into its cold tolerance divergence. A comparative study of the CBF pathway, associated with the cold tolerance enhancement of cold‐susceptible CBF 1 ‐transgenic plant, among four geographically distinct crofton weed populations revealed that the CBF pathway plays a key role in the observed cold tolerance divergence. Four epialleles of the cold response regulator ICE 1 ranged from 66 to 50 methylated cytosines, representing a 4.4% to 3.3% methylation rate and significantly corresponding to the lowest to highest cold tolerance levels among these different populations. The significant negative relation between the transcription levels of the primary CBF pathway members, except for CBF 2 , and the methylation levels among the four populations firstly demonstrates that the demethylation‐upregulated transcription level of CBF pathway is responsible for this evolution. These facts, combined with the cold tolerance variation and methylation found among three native and two other introduced populations, indicate that the ICE 1‐ demethylated upregulation of cold tolerance may be the underlying evolutionary mechanism allowing crofton weed to expand northward in China.

Use of ground-penetrating radar for construction monitoring and evaluation of perpetual pavements - Jiusu Li; Lubinda F. Walubita; Geoffrey S. Simate; Allex E. Alvarez; Wenting Liu (Natural Hazards, 2015)

Association of IL-18 promoter gene polymorphisms with rheumatoid arthritis: a meta-analysis - Li-Ping Cai; Li-Juan Zhou; Shun-Yu Lu; Ying-E Liang; Xiao-Ying Chen; Lin Liu; Jun Lin (Molecular Biology Reports, 2014)

Transcriptome profiling of CTLs regulated by rapamycin using RNA-Seq - Elliot Mattson; Lingyang Xu; Lei Li; George E. Liu; Zhengguo Xiao (Immunogenetics, 2014)

Gene-based SNP discovery and genetic mapping in pea - Anoop Sindhu; Larissa Ramsay; Lacey-Anne Sanderson; Robert Stonehouse; Rong Li; Janet Condie; Arun S. K. Shunmugam; Yong Liu; Ambuj B. Jha; Marwan Diapari; Judith Burstin; Gregoire Aubert; et al. (Theoretical and Applied Genetics, 2014)

Eutrophication as a driver of r ‐selection traits in a freshwater fish - M. Lin; M. Chevalier; S. Lek; L. Zhang; R. E. Gozlan; J. Liu; T. Zhang; S. Ye; W. Li; Z. Li (Journal of Fish Biology, 2014)
This study tested whether eutrophication could influence life‐history traits of a cyprinid, Chanodichthys erythropterus , in 10 Chinese lakes. Using the von Bertalanffy growth model, the asymptotic length ( L ∞ ) and the growth performance index ( I GRO ) were significantly affected by eutrophication. The gonado‐somatic index ( I G ) and relative fecundity ( F R ) were significantly lower in mesotrophic lakes than in eutrophic and hypertrophic lakes. These results indicate that increasing eutrophication affects the life‐history tactics of a freshwater fish.

Benthic Exchange of C, N, and P Along the Estuarine Ecotone of Lower Taylor Slough, Florida (USA): Effect of Seasonal Flows and Phosphorus Availability - Kung Jen Liu; Hsiu Ping Li; Stephen E. Davis (Wetlands, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Isolation and characterization of a mycorrhiza helper bacterium from rhizosphere soils of poplar stands - Liu Zhao; Xiao-Qin Wu; Jian-Ren Ye; Hao Li; Gui-E Li (Biology and Fertility of Soils, 2014)

Ecological suitability assessment and introduction experiment on Rosa damascena trigintipetala in Sichuan Province, China - Xiao-lan Wang; Chun-jiang Su; Li Peng; Hai-e Wang; Hai-ming Wang; Wei Liu; Ping Li; Yan Fang (Journal of Mountain Science, 2014)

Rapid growth increases intrinsic predation risk in genetically modified Cyprinus carpio : implications for environmental risk - L. Zhang; R. E. Gozlan; Z. Li; J. Liu; T. Zhang; W. Hu; Z. Zhu (Journal of Fish Biology, 2014)
The intrinsic effect of feeding regime on survival and predation‐induced mortality was experimentally tested in genetically modified ( GM ) Cyprinus carpio and wild specimens. The results clearly indicate a knock‐on effect of the GH gene ( gcGH ) introduction into the C. carpio genome on their vulnerability to predation. The experiments unequivocally showed that it is the genetic nature of the C. carpio rather than its size that affects the risk of predation. In addition, fed C. carpio were more susceptible to predation risk. Thus, the study characterizes the existence of a trade‐off between somatic growth and predator avoidance performance. Current research in Europe suggests that high uncertainty surrounding the potential environmental effects of escapee transgenic fishes into the wild is largely due to uncertainty in how the modified gene will be expressed. Understanding variables such as the cost of rapid growth on antipredator success would prove to be pivotal in setting up sound risk assessments for GM fishes and in fully assessing the environmental risk associated with GM fish escapees.

Identifying Explicit Formulation of Operating Rules for Multi-Reservoir Systems Using Genetic Programming - Liping Li; Pan Liu; David E. Rheinheimer; Chao Deng; Yanlai Zhou (Water Resources Management, 2014)

Peginterferon plus Chinese herbal therapy is associated with a higher virological response than only peginterferon therapy in chronic hepatitis C - D. Cheng; E. Liu; Y. Li; R. Liu; L. Bai; Y. Chen; Y. Wang; Y. Chu; M. Wu; G. Cheng; S. Zhao (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Genome-wide association study and meta-analysis of intraocular pressure - A. Bilge Ozel; Sayoko E. Moroi; David M. Reed; Melisa Nika; Caroline M. Schmidt; Sara Akbari; Kathleen Scott; Frank Rozsa; Hemant Pawar; David C. Musch; Paul R. Lichter; Doug Gaasterland; et al. (Human Genetics, 2014)

Accumulation of mercury in rice grain and cabbage grown on representative Chinese soils - Chun-fa Liu; Cheng-xian Wu; Muhammad T. Rafiq; Rukhsanda Aziz; Dan-di Hou; Zhe-li Ding; Zi-wen Lin; Lin-jun Lou; Yuan-yuan Feng; Ting-qiang Li; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Isolation and identification of phytate-degrading rhizobacteria with activity of improving growth of poplar and Masson pine - Gui-E Li; Xiao-Qin Wu; Jian-Ren Ye; Liang Hou; Ai-Dong Zhou; Liu Zhao (World Journal of Microbiology and Biotechnology, 2013)

Genomic comparison of Salmonella typhimurium DT104 with non-DT104 strains - Er-Ying Zhao; Hong-Xia Bao; Le Tang; Qing-Hua Zou; Wei-Qiao Liu; Da-Ling Zhu; Jessica Chin; Ying-Ying Dong; Yong-Guo Li; Feng-Lin Cao; Cornelis Poppe; Kenneth E. Sanderson; et al. (Molecular Genetics and Genomics, 2013)

A HPLC-based glycoanalytical protocol allows the use of natural O-glycans derived from glycoproteins as substrates for glycosidase discovery from microbial culture - Li Liu; Tharmala Tharmalingam; Eva Maischberger; Simone Albrecht; Mary E. Gallagher; Raúl Miranda-CasoLuengo; Wim G. Meijer; Pauline M. Rudd; Jane A. Irwin (Glycoconjugate Journal, 2013)

Biodegradation of high concentration of nitrobenzene by Pseudomonas corrugata embedded in peat-phosphate esterified polyvinyl alcohol - Na Liu; Hai-jun Li; Yue-e Shi; Bo-lin Zhu; Song Gao (World Journal of Microbiology and Biotechnology, 2013)

QTL mapping of stalk bending strength in a recombinant inbred line maize population - Haixiao Hu; Wenxin Liu; Zhiyi Fu; Linda Homann; Frank Technow; Hongwu Wang; Chengliang Song; Shitu Li; Albrecht E. Melchinger; Shaojiang Chen (Theoretical and Applied Genetics, 2013)

Increased Generation of Cyclopentenone Prostaglandins after Brain Ischemia and Their Role in Aggregation of Ubiquitinated Proteins in Neurons - Hao Liu; Wenjin Li; Muzamil Ahmad; Marie E. Rose; Tricia M. Miller; Mei Yu; Jie Chen; Jordan L. Pascoe; Samuel M. Poloyac; Robert W. Hickey; Steven H. Graham (Neurotoxicity Research, 2013)

Effects of Edaravone on Amyloid-β Precursor Protein Processing in SY5Y-APP695 Cells - Yue-E Shen; Yan Wang; Gui-Chun Yu; Chao Liu; Zhen-Yu Zhang; Li-Ming Zhang (Neurotoxicity Research, 2013)

Generation of minipigs with targeted transgene insertion by recombinase-mediated cassette exchange (RMCE) and somatic cell nuclear transfer (SCNT) - Jannik Ejnar Jakobsen; Marianne G. Johansen; Mette Schmidt; Frederik Dagnæs-Hansen; Karen Dam; Anders Gunnarsson; Ying Liu; Peter M. Kragh; Rong Li; Ida E. Holm; Henrik Callesen; Jacob Giehm Mikkelsen; et al. (Transgenic Research, 2013)

Fine mapping of qhir1 influencing in vivo haploid induction in maize - X. Dong; X. Xu; J. Miao; L. Li; D. Zhang; X. Mi; C. Liu; X. Tian; A. E. Melchinger; S. Chen (Theoretical and Applied Genetics, 2013)

Identification of a novel bluetongue virus 1-specific B-cell epitope using a monoclonal antibody against the VP2 protein - P. Wei; E. C. Sun; N. H. Liu; T. Yang; Q. Y. Xu; J. Zhao; Y. L. Qin; Y. F. Feng; J. P. Li; W. S. Wang; C. Y. Zhang; D. L. Wu (Archives of Virology, 2013)

Mechanisms of along-channel sediment transport in the North Passage of the Yangtze Estuary and their response to large-scale interventions - Chenjuan Jiang; Huib E. de Swart; Jiufa Li; Gaofeng Liu (Ocean Dynamics, 2013)

Investigation of transferability of BovineSNP50 BeadChip from cattle to water buffalo for genome wide association study - Jun Jing Wu; Li Jun Song; Fang Jie Wu; Xian Wei Liang; Bing Zhuang Yang; D. Claire Wathes; Geoff E. Pollott; Zhangrui Cheng; De Shun Shi; Qing You Liu; Li Guo Yang; Shu Jun Zhang (Molecular Biology Reports, 2013)

The melanocortin 1 receptor (MC1R) inhibits the inflammatory response in Raw 264.7 cells and atopic dermatitis (AD) mouse model - Wei Chen; Jianping Li; Hai’e Qu; Zhou Song; Zhanqing Yang; Jinlong Huo; Huaizhi Jiang; Qinghua Huang; Meixia Huo; Bo Liu; Qiaoling Zhang (Molecular Biology Reports, 2013)

In Vitro and In Vivo Evaluation of a Water-in-Oil Microemulsion System for Enhanced Peptide Intestinal Delivery - Dongyun Liu; Taku Kobayashi; Steven Russo; Fengling Li; Scott E. Plevy; Todd M. Gambling; Johnny L. Carson; Russell J. Mumper (The AAPS Journal, 2013)

Development of RT-LAMP and real-time RT-PCR assays for the rapid detection of the new duck Tembusu-like BYD virus - Tao Jiang; Juan Liu; Yong-Qiang Deng; Jing-Liang Su; Li-Juan Xu; Zhi-Hui Liu; Xiao-Feng Li; Xue-Dong Yu; Shun-Ya Zhu; George Fu Gao; E-De Qin; Cheng-Feng Qin (Archives of Virology, 2012)

Ion Composition of Fog Water and Its Relation to Air Pollutants during Winter Fog Events in Nanjing, China - Jun Yang; Yu-Jing Xie; Chun-E Shi; Duan-Yang Liu; Sheng-Jie Niu; Zi-Hua Li (Pure and Applied Geophysics, 2012)

Reducing progoitrin and enriching glucoraphanin in Braasica napus seeds through silencing of the GSL-ALK gene family - Zheng Liu; Arvind H. Hirani; Peter B. E. McVetty; Fouad Daayf; Carlos F. Quiros; Genyi Li (Plant Molecular Biology, 2012)

Genomic regions showing copy number variations associate with resistance or susceptibility to gastrointestinal nematodes in Angus cattle - Yali Hou; George E. Liu; Derek M. Bickhart; Lakshmi K. Matukumalli; Congjun Li; Jiuzhou Song; Louis C. Gasbarre; Curtis P. Van Tassell; Tad S. Sonstegard (Functional & Integrative Genomics, 2012)

Genetic analysis and fine mapping of the Ga1-S gene region conferring cross-incompatibility in maize - Hua Zhang; Xu Liu; Yu’e Zhang; Chuan Jiang; Dezhou Cui; Huaihua Liu; Detao Li; Liwen Wang; Tingting Chen; Lihua Ning; Xia Ma; Huabang Chen (Theoretical and Applied Genetics, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Pig transgenesis by Sleeping Beauty DNA transposition - Jannik E. Jakobsen; Juan Li; Peter M. Kragh; Brian Moldt; Lin Lin; Ying Liu; Mette Schmidt; Kjeld Dahl Winther; Brian Dall Schyth; Ida E. Holm; Gábor Vajta; Lars Bolund; et al. (Transgenic Research, 2011)

Molecular cloning, tissue expression and association of porcine NR4A1 gene with reproductive traits - L. Q. Liu; F. E. Li; C. Y. Deng; Y. Z. Xiong (Molecular Biology Reports, 2011)

Treatment with peginterferon versus interferon in Chinese patients with chronic hepatitis C - S. Zhao; E. Liu; K. Wei; Y. Wang; Y. Li; B. Huang; Y. Chen; P. Yang (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Globular adiponectin regulates energy homeostasis through AMP-activated protein kinase–acetyl-CoA carboxylase (AMPK/ACC) pathway in the hypothalamus - Jun-Ping Wen; Chun-e Liu; Ya-Ting Hu; Gang Chen; Li-xiang Lin (Molecular and Cellular Biochemistry, 2010)

Large-Eddy Simulation of Flow and Pollutant Transport in Urban Street Canyons with Ground Heating - Xian-Xiang Li; Rex E. Britter; Tieh Yong Koh; Leslie K. Norford; Chun-Ho Liu; Dara Entekhabi; Dennis Y. C. Leung (Boundary-Layer Meteorology, 2010)

Identification of QTL for oil content, seed yield, and flowering time in oilseed rape (Brassica napus) - Gang Chen; Jianfeng Geng; Mukhlesur Rahman; Xueping Liu; Jingxing Tu; Tingdong Fu; Gengyi Li; Peter B. E. McVetty; M. Tahir (Euphytica, 2010)

Chrysanthemum genetic resources and related genera of Chrysanthemum collected in China - H. E. Zhao; Z. H. Liu; X. Hu; J. L. Yin; W. Li; G. Y. Rao; X. H. Zhang; C. L. Huang; N. Anderson; Q. X. Zhang; J. Y. Chen (Genetic Resources and Crop Evolution, 2009)

Human papillomavirus type-distribution in cervical cancer in China: the importance of HPV 16 and 18 - Wen Chen; Xun Zhang; Anco Molijn; David Jenkins; Ju-Fang Shi; Wim Quint; Johannes E. Schmidt; Ping Wang; Yu-Ling Liu; Lian-Kun Li; Hong Shi; Ji-Hong Liu; et al. (Cancer Causes & Control, 2009)

The complete nucleotide sequence and genome organization of tomato infectious chlorosis virus: a distinct crinivirus most closely related to lettuce infectious yellows virus - William M. Wintermantel; Laura L. Hladky; Anju Gulati-Sakhuja; Ruhui Li; Hsing-Yeh Liu; Ioannis E. Tzanetakis (Archives of Virology, 2009)

Stock enhancement of the edible jellyfish (Rhopilema esculentum Kishinouye) in Liaodong Bay, China: a review - Jing Dong; Lian-xin Jiang; Ke-fei Tan; Hai-ying Liu; Jennifer E. Purcell; Pei-jun Li; Chang-chen Ye (Hydrobiologia, 2009)

Association of MYF5 and MYOD1 Gene Polymorphisms and Meat Quality Traits in Large White × Meishan F2 Pig Populations - Min Liu; Jian Peng; De-Quan Xu; Rong Zheng; Feng-E Li; Jia-Lian Li; Bo Zuo; Ming-Gang Lei; Yuan-Zhu Xiong; Chang-Yan Deng; Si-Wen Jiang (Biochemical Genetics, 2008)

Functional analysis reveals pleiotropic effects of rice RING-H2 finger protein gene OsBIRF1 on regulation of growth and defense responses against abiotic and biotic stresses - Huizhi Liu; Huijuan Zhang; Yayun Yang; Guojun Li; Yuxia Yang; Xiao’e Wang; B. M. Vindhya S. Basnayake; Dayong Li; Fengming Song (Plant Molecular Biology, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Enhancement of Lead Uptake by Hyperaccumulator Plant Species Sedum alfredii Hance Using EDTA and IAA - D. Liu; T. Li; X. Yang; E. Islam; X. Jin; Q. Mahmood (Bulletin of Environmental Contamination and Toxicology, 2007)

A comparative linkage map of oilseed rape and its use for QTL analysis of seed oil and erucic acid content - D. Qiu; C. Morgan; J. Shi; Y. Long; J. Liu; R. Li; X. Zhuang; Y. Wang; X. Tan; E. Dietrich; T. Weihmann; C. Everett; et al. (Theoretical and Applied Genetics, 2006)

An autosomal genomic scan for loci linked to type 2 diabetes in northern Han Chinese - J. Y. Zhao; M. M. Xiong; W. Huang; H. Wang; J. Zuo; G. D. Wu; Z. Chen; B. Q. Qiang; M. L. Zhang; J. L. Chen; W. Ding; W. T. Yuan; et al. (Journal of Molecular Medicine, 2005)

Characterization of Usher syndrome type I gene mutations in an Usher syndrome patient population - Xiao Mei Ouyang; Denise Yan; Li Lin Du; J. Fielding. Hejtmancik; Samuel G. Jacobson; Walter E. Nance; An Ren Li; Simon Angeli; Muriel Kaiser; Valerie Newton; Steve D. M. Brown; Thomas Balkany; et al. (Human Genetics, 2005)

QTL × environment interactions in rice. I. Heading date and plant height - Z. K. Li; S. B. Yu; H. R. Lafitte; N. Huang; B. Courtois; S. Hittalmani; C. H. M. Vijayakumar; G. F. Liu; G. C. Wang; H. E. Shashidhar; J. Y. Zhuang; K. L. Zheng; et al. (Theoretical and Applied Genetics, 2003)

Evidence of a founder effect for the 235delC mutation of GJB2 (connexin26) in east Asians - Denise Yan; Hong-Joon Park; Xiao Mei Ouyang; Arti Pandya; Katsumi Doi; Raadnabazar Erdenetungalag; Li Lin Du; Naoki Matsushiro; Walter E. Nance; Andrew J. Griffith; Xue Zhong Liu (Human Genetics, 2003)

Characterisation of the expression of a novel constitutive maize promoter in transgenic wheat and maize - S. Rasco-Gaunt; D. Liu; C. Li; A. Doherty; K. Hagemann; A. Riley; T. Thompson; C. Brunkan; M. Mitchell; K. Lowe; E. Krebbers; P. Lazzeri; et al. (Plant Cell Reports, 2003)

Mutations in the alternatively spliced exons of USH1C cause non-syndromic recessive deafness - Xiao Ouyang; Xia Xia; Elisabeth Verpy; Li Du; Arti Pandya; Christine Petit; Thomas Balkany; Walter E. Nance; Xue Liu (Human Genetics, 2002)

Palaeovegetation of China: a pollen data‐based synthesis for the mid‐Holocene and last glacial maximum - G. Yu; X. Chen; J. Ni; R. Cheddadi; J. Guiot; H. Han; S. P. Harrison; C. Huang; M. Ke; Z. Kong; S. Li; W. Li; et al. (Journal of Biogeography, 2000)
Pollen data from China for 6000 and 18,000 14 C yr bp were compiled and used to reconstruct palaeovegetation patterns, using complete taxon lists where possible and a biomization procedure that entailed the assignment of 645 pollen taxa to plant functional types. A set of 658 modern pollen samples spanning all biomes and regions provided a comprehensive test for this procedure and showed convincing agreement between reconstructed biomes and present natural vegetation types, both geographically and in terms of the elevation gradients in mountain regions of north‐eastern and south‐western China. The 6000 14 C yr bp map confirms earlier studies in showing that the forest biomes in eastern China were systematically shifted northwards and extended westwards during the mid‐Holocene. Tropical rain forest occurred on mainland China at sites characterized today by either tropical seasonal or broadleaved evergreen/warm mixed forest. Broadleaved evergreen/warm mixed forest occurred further north than today, and at higher elevation sites within the modern latitudinal range of this biome. The northern limit of temperate deciduous forest was shifted c. 800 km north relative to today. The 18,000 14 C yr bp map shows that steppe and even desert vegetation extended to the modern coast of eastern China at the last glacial maximum, replacing today’s temperate deciduous forest. Tropical forests were excluded from China and broadleaved evergreen/warm mixed forest had retreated to tropical latitudes, while taiga extended southwards to c . 43°N.

Genomic mapping of defense response genes in wheat - W. L. Li; J. D. Faris; J. M. Chittoor; J. E. Leach; S. H. Hulbert; D. J. Liu; P. D. Chen; B. S. Gill (Theoretical and Applied Genetics, 1999)

Identification and genetic mapping of Xenopus TAP2 genes - Y. Ohta; S. J. Powis; W. John Coadwell; Darren E. Haliniewski; Y. Liu; Hong Li; M. F. Flajnik (Immunogenetics, 1999)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

In Vivo Gene Transfer by Intravenous Administration of Stable Cationic Lipid/DNA Complex - Hans E. J. Hofland; Dea Nagy; Jing-Jie Liu; Kaye Spratt; Ya-Li Lee; Olivier Danos; Sean M. Sullivan (Pharmaceutical Research, 1997)